Precipitated silica and its manufacturing method
The tailored precipitated silica with controlled surface area and particle size distribution addresses the balance of mechanical properties and dispersion in elastomeric compositions, improving reinforcement and temperature stability.
Patent Information
- Application Number
- JP2024535785
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-23
- Filing Date
- 2022-12-21
- Publication Date
- 2025-01-17
AI Technical Summary
Existing precipitated silicas used as reinforcing fillers in elastomeric compositions face challenges in achieving a balance between high hysteresis at low temperatures and low hysteresis at high temperatures, along with inconsistent reinforcement and dispersion efficiency.
The development of precipitated silica with specific surface area (CTAB) between 40-300 m²/g, average particle size less than 11 nm, and controlled particle size distribution, characterized by a median particle size (d50) that follows the relation |d50| <-0.782×|CTAB| + 255, enhances mechanical properties and dispersion in elastomer compositions.
The optimized silica composition improves mechanical properties and dispersion in elastomeric compositions, providing enhanced reinforcement and temperature stability.
Smart Images

Figure 2025501077000001 
Figure 2025501077000002 
Figure 2025501077000003
Abstract
Description
[Technical field]
[0001] The present invention relates to precipitated silica and to a process for its preparation. The present invention further relates to the use of precipitated silica as a reinforcing filler in polymer compositions, preferably elastomeric compositions. [Background technology]
[0002] The use of precipitated silica as a reinforcing filler in polymer compositions is known. In particular, the use of precipitated silica as a reinforcing filler in elastomeric compositions is known. Such use is very demanding: the filler must be easily and efficiently incorporated and dispersed in the elastomeric composition, and must enter into chemical bonds with the elastomer, typically with a coupling agent, resulting in high and homogeneous reinforcement of the elastomeric composition. In general, precipitated silica is used to improve the mechanical properties, handling, and wear performance of the elastomeric composition.
[0003] WO 2020 / 094717 in the name of the applicant describes the use of surface area (i.e. CTAB) and particle size (i.e. d ) to obtain a good balance between the properties of the elastomeric composition: high hysteresis at low temperatures and low hysteresis at high temperatures with comparable reinforcement index (tensile properties) and compound processability. 50 ) is disclosed. 50 must be higher than a given value that increases when the surface area CTAB of the silica decreases.
[0004] WO 03 / 016215 in the name of the Applicant discloses precipitated silicas having certain properties, namely in terms of particle size distribution (measured by XDC or X-ray disc centrifuge) and porosity, which function very well as reinforcing agents for elastomeric compositions, but the Applicant has now found that they can be further improved in terms of the mechanical properties of the elastomeric compositions. Summary of the Invention [Means for solving the problem]
[0005] Features include: 40~300m 2 CTAB surface area in the range of / g; Average size d less than 11 nm measured by SAXS ZS Primary particles having Measured by centrifugal sedimentation |d 50 |<-0.782×|CTAB|+255(I) The median particle size d 50 ; It has been found that the use of precipitated silica having DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] As used herein, the terms "silica" and "precipitated silica" are used synonymously.
[0007] In this specification, a numerical range defined by the expression "between a and b" indicates a numerical range excluding the end values a and b, and a numerical range defined by the expression "from a to b" indicates a numerical range including the end values a and b.
[0008] A numerical range defined by the expression "a is at least b" indicates a range in which a is equal to or greater than b.
[0009] For the avoidance of doubt, it is specified that the symbol "x" in formula (I) represents a multiplication symbol, so that the expression "a x b" means a multiplied by b.
[0010] The term particle is used to refer to the smallest aggregates of primary silica particles that can be broken by mechanical action. In other words, the term "particle" refers to an assembly / agglomerate of primary particles that cannot be divided, said aggregates having a median particle size d50 whereas the undivided primary particles are characterized by a claimed average size.
[0011] In formula (I), |CTAB| is m 2 This is the numerical value of the CTAB surface area expressed in g / g. |CTAB| is a dimensionless number. For example, if the measured CTAB is 200 m 2 / g, then |CTAB| is 200. The same applies to the other values between || below, which are all dimensionless numerical values of the parameters between the vertical bars.
[0012] CTAB surface area is a measure of the external specific surface area determined by measuring the amount of N-hexadecyl-N,N,N-trimethylammonium bromide adsorbed on the silica surface at a given pH. CTAB surface area is at least 40 m 2 / g, typically at least 60m 2 / g. The surface area of CTAB is 70 m 2 / g. The CTAB surface area can be further increased to 110 m 2 / g, 120m 2 / g, 130m 2 / g, and in some cases even 150m 2 / g.
[0013] CTAB surface area is 300m 2 / g. The CTAB surface area is 280 m 2 / g, 250m 2 / g, less than 230m 2 / g, and in some cases even 210m 2 / g, less than 190m 2 / g, less than 180m 2 / g or less than 170m 2 / g.
[0014] The range of CTAB surface area that is particularly advantageous for elastomer reinforcement applications is 50-300m 2 / g, preferably 70 to 300m 2 / g, more preferably 80 to 270m2 / g, or 120~275m 2 / g. In particular, the CTAB surface area is 70m 2 / g greater than 250m 2 / g, especially when the CTAB surface area is less than 110 m 2 / g or greater than 210m 2 / g, more specifically, when the CTAB surface area is less than 130 m 2 / g greater than 180m 2 Good results were obtained when the .mu.m was less than 1 / g.
[0015] The BET surface area of the silica of the present invention is not particularly limited, but is preferably at least 10 m2 greater than the CTAB specific surface area. 2 / g. The BET surface area is typically at least 80 m 2 / g, at least 100m 2 / g, at least 120m 2 / g, at least 140m 2 / g, at least 160m 2 / g, at least 170m 2 / g, at least 180m 2 / g, and at least 200m 2 / g. The BET surface area is 300 m 2 / g, and even 350m 2 / g, and the BET surface is up to 260m 2 / g, up to 240m 2 / g, up to 220m 2 / g, and in some cases up to 200m 2 / g, up to 180m 2 / g, or up to 170m 2 In many embodiments, the BET surface area is greater than 100 m 2 / g~300m 2 / g.
[0016] The difference between the BET surface area and the CTAB surface area is generally taken to represent the microporosity of precipitated silica, in that it provides a measure of the pores in the silica that are accessible to nitrogen molecules but not to larger molecules such as N-hexadecyl-N,N,N-trimethylammonium bromide.
[0017] The precipitated silica of the present invention preferably has a particle size of at least 5 mm 2 / g, preferably at least 10m 2 / g, the difference between the BET surface area and the CTAB surface area is preferably 40 m 2 / g or less, more preferably 35m 2 / g or less.
[0018] The silica of the present invention may be essentially free or even completely free of aluminum. The silica of the present invention may be present in an amount W of less than 0.50% by weight, preferably less than 0.45% by weight, typically at least 0.01% by weight and less than 0.50% by weight, preferably at least 0.01% by weight and less than 0.45% by weight. Al Alternatively, the aluminum may be present in an amount W of at least 0.50% by weight and typically up to 3.00% by weight, usually up to 5.00% by weight or up to 7.00% by weight. Al The specific suitable aluminum range W Al is from 0.01% by weight to less than 0.25% by weight (particularly from 0.05% by weight to less than 0.25% by weight), and from 0.25% by weight to less than 0.50% by weight (particularly from 0.25% by weight to less than 0.45% by weight). Alis 0.50 wt% to 1.50 wt%, particularly 0.50 wt% to 1.00 wt%, and more than 1.50 wt% to 3.00 wt%. For the avoidance of doubt, the term "less than" is used herein in its ordinary and generally accepted sense, i.e., "below a particular amount or level," particularly as found in Cambridge's Dictionary (available online at https: / / dictionary.cambridge.org / dictionary / english / below). Similarly, the term "lower" is used herein in its ordinary and generally accepted sense, i.e., "located below," particularly as found in Cambridge's Dictionary. Thus, the terms "less than" and "lower" as used herein have the same meaning as their ordinary and generally accepted meaning. Throughout this specification, the amount of aluminum W Al SiO 2 The percentage by weight of aluminum, in terms of aluminum metal, relative to the weight of the precipitated silica, is defined as the weight percent of aluminum. The amount of aluminum is preferably measured using XRF wavelength dispersive X-ray fluorescence spectroscopy. This aluminum usually originates at least in part from the raw materials. In some embodiments, an aluminum compound (such as sodium aluminate) is added during the synthesis of the precipitated silica and / or during the liquefaction process as described below.
[0019] It should be understood that the silica of the present invention may contain elements, such as, but not limited to, Al, Ga, B, Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Fe, Co, Mg, Ca, or Zn. Thus, in one embodiment, the silica of the present invention contains at least one element selected from Al, Ga, B, Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Fe, Co, Mg, Ca, or Zn, and in particular, the silica of the present invention may contain Al and at least one element selected from Ga, B, Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Fe, Co, Mg, Ca, and Zn.
[0020] The precipitated silica of the present invention further has a median particle size d measured by the small size of the primary particles and by centrifugal sedimentation. 50 corresponds to the above relation (I).
[0021] The d of the precipitated silica according to the invention, determined by centrifugal sedimentation in a disc centrifuge using the CPS detailed below. 50 is typically comprised between 50 and 200 nm, preferably between 75 and 150 nm, possibly between 85 and 130 nm, in particular between 95 and 120 nm. 50 represents the particle size below (or above) which 50% of the total mass of the particles actually lies. Therefore, d 50 represents the median particle size of a given distribution, and the term "size" in this context is intended to mean "diameter."
[0022] As defined above, the d of the precipitated silica according to the invention 50 obeys the relation (I): |d 50 |<-0.782×|CTAB|+255 (I).
[0023] Optionally, the precipitated silica according to the invention 50 is expressed by the relation (I 1 ) according to: |d 50 | <k 1 ×(-0.782×|CTAB|+255) (I 1 ) (In the formula, k 1 is a dimensionless number, equal to 0.950).
[0024] In addition, the precipitated silica according to the present invention 50 is usually expressed by the relation (I 2 ) according to: |d 50 |>k 2 ×(-0.782×|CTAB|+255) (I 2 ) (In the formula, k 2 is a dimensionless number, which is 0.750).
[0025] In many cases, the precipitated silica according to the invention 50 is expressed by the relation (I 3 ) according to: |d 50 |>k 3 ×(-0.782×|CTAB|+255) (I 3 ) (In the formula, k 3 is a dimensionless number, equal to 0.800).
[0026] The precipitated silica according to the invention 50 is represented by the formula (I) and ( 2 ) can be obeyed. In addition, the relationship (I) and ((I 3 ) can also be obeyed. 1 ) and (I 2 ) can also be obeyed. 1 ) and (I 3 ) can also be followed.
[0027] The precipitated silica according to the invention has a size d measured by SAXS (small angle X-ray scattering (SAXS) as described below) of less than 11 nm, preferably less than 10 nm, and more preferably less than 9 nm. ZS Typically, the size of the primary particles is greater than 4 nm, preferably greater than 5 nm, more preferably greater than 6 nm. ZS A particular suitable range of is 5 to 11 nm, preferably 6 to 10 nm. Typically, the primary particles of silica according to the present invention all have a particle size in the same range (usually 5 to 15 nm, preferably 5 to 11 nm, more preferably 6 to 10 nm), which means that in practice there is only one population of primary particles based on the SAXS measurement profile.
[0028] The silica of the present invention 84 is preferably characterized by the following formula: |d 84 |<-2.08×|CTAB|+659(II). Typically, this d 84 is included in the range of 120 to 430 nm, preferably 150 to 400 nm.
[0029] The L of the precipitated silica according to the invention d is typically at least 1.00, generally at least 1.10, preferably at least 1.25, and more preferably at least 1.30. d The L of the silica of the present invention is usually 2.10 or less, typically 2.00 or less. d is preferably 1.00 to 2.10, more preferably 1.10 to 2.00. d is defined as follows: L d =(d 84 -d 16 ) / d 50 (d in the formula n L is the particle size below which n% of the total measured mass falls. d is a dimensionless number calculated on the cumulative particle size curve.
[0030] The parameter FWHM, also determined by centrifugal sedimentation in a disc centrifuge using the CPS detailed below, can also be used to characterize the width of the particle size distribution of the precipitated silica according to the invention. The FWHM (or full width at half maximum) is obtained from the CPS derivative curve. The FWHM measures the distribution width of the silica objects around the average size (in nm) defined by the mode. If the FWHM is large around the average value, the silica product is inhomogeneous. If the FWHM is sharp around the average value, the silica product is more homogeneous. In the case of a Gaussian particle size distribution (which is rare in practice), the parameter FWHM is the function of the parameter L d Correlated with.
[0031] The FWHM of the precipitated silica according to the invention is preferably: |FWHM|<250-0.815×|CTAB| (III) It is.
[0032] The fine particle fraction (τf), i.e. the proportion (by weight) of particles less than 1 μm in size after ultrasonic deagglomeration (determined by the "Sedigraph" test method described below), is also a way of indicating the dispersibility of the precipitated silica according to the invention. In a preferred embodiment, this fine particle fraction is τf such that |τf|>=0.045×|CTAB|+84 (IV). This formula is applicable to any precipitated silica, whatever its form. This formula is also applicable in particular to non-granulated products, i.e. powders or micropearls. This formula is also applicable to granules.
[0033] Strictly speaking, the form of the precipitated silica of the present invention is not particularly limited. Thus, the silica of the present invention can be in a form selected from the group consisting of powder, substantially spherical beads (commonly called "micropearls"), granules, and mixtures thereof. In some embodiments, it is in the form of a powder. In some other embodiments, it is in the form of micropearls. In yet other embodiments, it is in the form of granules.
[0034] A second object of the present invention is a process for the preparation of precipitated silica, comprising the steps of: (i) preparing a starting solution having a pH of 2.00 to 5.50; (ii) adding silicate and acid simultaneously to said starting solution to obtain a reaction medium whose pH is maintained in the range of 2.00 to 5.50; (iii) stopping the addition of acid and silicate and adding a base to the reaction medium to increase the pH of said reaction medium to a value between 7.00 and 10.00; (iv) adding silicate and acid simultaneously to the reaction medium so as to maintain the pH of the reaction medium in the range of 7.00 to 10.00; (v) continuing said addition of said acid to said reaction medium while stopping the addition of said silicate salt to reach a pH of said reaction medium of less than 6.00 to obtain a suspension of precipitated silica; Including, a gel point is reached during step (ii), and the amount of silicate added during step (ii) after the gel point is reached is between 5% and 55% of the total amount of silicate added at the end of step (ii).
[0035] Said method is particularly suitable for the preparation of the precipitated silica of the first object. Thus, said second object of the invention is advantageously a method for the preparation of the precipitated silica of the first object, comprising: (i) preparing a starting solution having a pH of 2.00 to 5.50; (ii) adding silicate and acid simultaneously to said starting solution to obtain a reaction medium whose pH is maintained in the range of 2.00 to 5.50; (iii) stopping the addition of acid and silicate and adding a base to the reaction medium to increase the pH of said reaction medium to a value between 7.00 and 10.00; (iv) adding silicate and acid simultaneously to the reaction medium so as to maintain the pH of the reaction medium in the range of 7.00 to 10.00; (v) continuing said addition of said acid to said reaction medium while stopping the addition of said silicate salt to reach a pH of said reaction medium of less than 6.00 to obtain a suspension of precipitated silica; Including, a gel point is reached during step (ii), and the amount of silicate added during step (ii) after the gel point is reached is between 5% and 55% of the total amount of silicate added at the end of step (ii).
[0036] The term "base" as used herein means one or more bases that may be added during the process of the present invention, which includes the group consisting of silicates as defined below. Any base may be used in the process. In the addition of silicates, notable non-limiting examples of suitable bases are, for example, alkali metal hydroxides and ammonia. Preferably, the base is a silicate, more preferably the same silicate as that used in the process.
[0037] The term "silicate" is used herein to refer to one or more silicates that may be added during the course of the process of the present invention. The silicate is typically selected from the group consisting of alkali metal silicates. The silicate is advantageously selected from the group consisting of sodium silicate and potassium silicate. The silicate may be in any known form, such as metasilicate or disilicate. It may be sourced from a variety of materials, such as sand, natural sources containing burnt silica (such as RHA or rice husk ash) or intact silica, or even from waste materials (such as from construction or mining).
[0038] If sodium silicate is used, the latter will usually have a SiO of 2.0 to 4.0, in particular 2.4 to 3.9, for example 3.1 to 3.8. 2 / Na 2 O weight ratio.
[0039] The silicate has a concentration of 3.9% by weight to 25.0% by weight, for example 5.6% by weight to 23.0% by weight, specifically 5.6% by weight to 21% by weight (SiO 2 (expressed in terms of
[0040] The term "acid" is used herein to refer to one or more acids that may be added during the course of the process of the present invention. Any acid may be used in the process. Typically, mineral acids such as sulfuric acid, nitric acid, phosphoric acid, or hydrochloric acid, or organic acids such as carboxylic acids, e.g., acetic acid, formic acid, or carbonic acid, are used. Good results have been obtained with sulfuric acid.
[0041] The acid can be metered into the reaction medium in dilute or concentrated form. Different concentrations of the same acid can be used at different stages of the process. Preferably, dilute acid is used until the gel point is reached (which occurs during step (ii)) and concentrated acid is used after the gel point is reached. Preferably, the dilute acid is dilute sulfuric acid (i.e. at a concentration much lower than 80% by weight, preferably less than 20% by weight, usually less than 14% by weight, in particular less than or equal to 10% by weight, for example between 5% and 10% by weight). Advantageously, the concentrated acid is concentrated sulfuric acid, i.e. at a concentration of at least 80% by weight (and generally less than or equal to 98% by weight), preferably at least 90% by weight; in particular, the concentration is between 90% by weight and 98% by weight, for example between 91% and 97% by weight.
[0042] In a preferred embodiment of the process, sulfuric acid and sodium silicate are used in all stages of the process. 2 The same sodium silicate is used in all of the process steps, that is, sodium silicate having the same concentration expressed as
[0043] In step (i) of the process, a starting solution having a pH of 2.00 to 5.50 is provided in a reaction vessel. The starting solution is typically an aqueous solution, the term "aqueous" indicating that the solvent is water.
[0044] Preferably, the starting solution has a pH of 2.50 to 5.50, in particular 3.00 to 4.50, for example 3.50 to 4.50.
[0045] The starting solution can be obtained by adding acid to water so as to obtain the pH values mentioned above.
[0046] The starting solution can also be prepared by adding an acid to a solution containing preformed silica particles having a pH of less than 7.00, preferably less than 6.00, to obtain a pH value of 2.00 to 5.00, preferably 2.50 to 5.00, in particular 3.00 to 4.50, for example 3.50 to 4.50.
[0047] The starting solution in step (i) may or may not contain an electrolyte, preferably the starting solution in step (i) contains an electrolyte to aid in recycling the water stream in the process.
[0048] The term "electrolyte" is used herein in its generally accepted sense, i.e. to identify any ionic or molecular substance that, when in solution, decomposes or dissociates to form ions or charged particles. The term "electrolyte" is used herein to indicate that one or more electrolytes may be present. Electrolytes such as salts of alkali metals and alkaline earth metals may be mentioned. Advantageously, the electrolyte used in the starting solution is a salt of the metal and acid of the starting silicate used in the process. Notable examples are, for example, sodium chloride in the case of the reaction of sodium silicate with hydrochloric acid or, preferably, sodium sulfate in the case of the reaction of sodium silicate with sulfuric acid. Preferably, the electrolyte does not include aluminum.
[0049] Preferably, when sodium sulfate is used as electrolyte in step (i), its concentration in the starting solution is between 5 and 40 g / L, in particular between 8 and 30 g / L, for example between 10 and 25 g / L.
[0050] Step (ii) of the process comprises the simultaneous addition of an acid and a silicate to the starting solution. The rates of addition of the acid and the silicate during step (ii) are controlled so as to maintain the pH of the reaction medium in the range of 2.00 to 5.50. The pH of the reaction medium is preferably maintained in the range of 2.50 to 5.00, in particular 3.00 to 5.00, for example 3.20 to 4.80.
[0051] The simultaneous addition in step (ii) is advantageously carried out so that the pH value of the reaction medium is always equal (to within ±0.20 pH units) to the pH reached at the end of step (i).
[0052] According to the invention, the amount of silicate added during step (ii) after the gel point is reached is 5% to 55% of the total amount of silicate added during step (ii), preferably 10% to 50%, more preferably 15% to 45% of the total amount of silicate added during step (ii). The gel point is defined as the point at which the viscosity of the reaction medium changes abruptly, which can be determined by measuring the torque of the stirrer. Usually, the stirring torque increases by 20% to 60% compared to the torque value before the gel point, preferably by 25% to 55%, more preferably by 30% to 50% compared to the torque value before the gel point.
[0053] In one embodiment of the process of the invention, an intermediate step (ii') may be carried out between steps (i) and (ii), in which silicate is added to the starting solution. If this optional step is carried out, an acid is then added in order to reach a suitable pH for step (ii). The pH value reached during this step is about 8.00 + / - 0.50.
[0054] Then, in step (iii), the addition of acid and silicate is stopped and a base is added to the reaction medium, the addition of the base being stopped when the pH of the reaction medium reaches a value between 7.00 and 10.00, preferably between 7.50 and 9.50.
[0055] In a first embodiment of the process the base is a silicate. Thus, in step (iii), the addition of the acid is stopped whilst the addition of the silicate to the reaction medium is continued until a pH of between 7.00 and 10.00, preferably between 7.50 and 9.50, is reached.
[0056] In a second embodiment of the method, the base is different from the silicate and is selected from the group consisting of alkali metal hydroxides, preferably sodium or potassium hydroxide. When sodium silicate is used in the method, the preferred base may be sodium hydroxide.
[0057] Thus, in this second embodiment of the process, in step (iii), the addition of acid and silicate is stopped and a base different from the silicate is added to the reaction medium until a pH of between 7.00 and 10.00, preferably between 7.50 and 9.50, is reached.
[0058] At the end of step (iii), i.e. after the addition of the base has been stopped, it may be advantageous to carry out an ageing step of the reaction medium. This step is preferably carried out at the pH obtained at the end of step (iii). The ageing step may be carried out whilst stirring the reaction medium. It is preferably carried out for a period comprised between 2 and 45 minutes, in particular between 5 and 25 minutes, whilst stirring the reaction medium. The ageing step preferably does not involve the addition of any acid or silicate.
[0059] After step (iii) and the optional maturation step, the simultaneous addition of acid and silicate is carried out so as to maintain the pH of the reaction medium in the range of from 7.00 to 10.00, preferably from 7.50 to 9.50.
[0060] The simultaneous addition of acid and silicate (step (iv)) is typically carried out in such a way that the pH value of the reaction medium is maintained equal (to within ±0.20 pH units) to the pH reached at the end of the previous step, i.e. step (iii).
[0061] Preferably, the amount of silicate added to the reaction medium during step (iv) is at least 55% of the total amount of silicate required for the reaction.
[0062] It should be noted that the method of the present invention may comprise further steps. For example, an acid may be added to the reaction medium between step (iii) and step (iv), in particular between the optional maturation step after step (iii) and step (iv). The pH of the reaction medium after this addition of acid should remain in the range of 7.00 to 9.50, preferably 7.50 to 9.50.
[0063] In step (v), the addition of silicate is stopped whilst continuing the addition of acid to the reaction medium in order to obtain a pH value in the reaction medium of less than 6.00, preferably between 3.00 and 5.50, in particular between 3.00 and 5.00. A suspension of precipitated silica is obtained in the reaction vessel.
[0064] At the end of step (v), thus after the addition of acid to the reaction medium has been stopped, an ageing step can advantageously be carried out, which can be carried out at the same pH obtained at the end of step (v) and under the same time conditions as those described above for the ageing step that can optionally be carried out between steps (iii) and (iv) of the process.
[0065] The reaction vessel in which the entire reaction between the silicate and the acid is carried out is usually equipped with suitable stirring and heating devices.
[0066] The overall reaction of the silicate with the acid (steps (i) to (v)) is usually carried out at a temperature of 40 to 97°C, particularly 60 to 95°C, preferably 80 to 95°C, and more preferably 85 to 95°C.
[0067] According to one variant of the invention, the overall reaction of silicate with acid is carried out at a constant temperature, usually between 40 and 97°C, in particular between 80 and 95°C and even better between 85 and 95°C.
[0068] According to another variant of the invention, the temperature at the end of the reaction is higher than the temperature at the beginning of the reaction, therefore the temperature at the beginning of the reaction (e.g. during steps (i) to (iii)) is preferably maintained in the range of 40 to 85° C., the temperature is then preferably raised to a value in the range of 80 to 95° C. or even 85 to 95° C. and maintained at that value until the end of the reaction (e.g. during steps (iv) and (v)).
[0069] At the end of the step just described, a suspension of precipitated silica is obtained which is subsequently separated (liquid / solid separation). The method typically comprises a further step (vi) of filtering the suspension and drying the precipitated silica.
[0070] The separation carried out in the preparation process according to the invention usually comprises a filtration, optionally followed by washing, which is carried out according to any suitable method, for example by means of a belt filter, a rotary filter, for example a vacuum filter or preferably a filter press.
[0071] The filter cake is then typically subjected to a liquefaction operation. The term "liquefaction" is intended herein to refer to the process by which a solid, i.e., the filter cake, is converted into a fluid mass, typically by the addition of a liquid, typically water or an aqueous medium. After the liquefaction step, the filter cake is in a flowable, fluid-like form and the precipitated silica is in suspension.
[0072] The liquefaction step may include a mechanical treatment that results in a reduction in the particle size distribution of the suspended silica. The mechanical treatment may be carried out by passing the filter cake through a high shear mixer, an extruder, a colloid mill or a ball mill. Alternatively, the liquefaction step may be carried out by subjecting the filter cake to chemical action, for example by adding an acid (inorganic or organic) or an aluminum compound, for example sodium aluminate. Alternatively, the liquefaction step may include both mechanical and chemical action.
[0073] The suspension of precipitated silica obtained after the optional liquefaction step is then preferably treated with additional chemicals, such as organics (for example polycarboxylic acids), and finally dried.
[0074] This drying can be carried out according to the techniques known in the art. Preferably, drying is carried out by spraying. Any type of suitable atomizer can be used for this purpose, in particular turbine, nozzle, liquid pressure or two-fluid spray dryer. Generally, when filtration is carried out using a filter press, a nozzle type atomizer is used, and when filtration is carried out using a vacuum filter, a turbine type atomizer is used.
[0075] If the drying operation is carried out using a nozzle spray dryer, the precipitated silica obtained thereafter is usually in the form of substantially spherical beads, commonly called "micropearls". After this drying operation, the recovered product can optionally be subjected to a grinding or pulverizing step, and the precipitated silica obtained is generally in the form of a powder. After this drying operation, the recovered micropearls can optionally be subjected to an agglomeration step, for example consisting of direct compression, wet granulation, extrusion or preferably dry compaction. The precipitated silica obtained thereafter is generally in the form of granules.
[0076] If the drying operation is carried out by means of a turbine spray dryer, the precipitated silica obtainable then may be in the form of a powder.
[0077] In one embodiment of the present invention, the filter cake does not undergo a liquefaction step and is directly dried by spin flash drying (eg, Hosokawa process).
[0078] Finally, the product dried, ground or pulverized as indicated above may optionally be subjected to an agglomeration step, which consists, for example, of direct compression, wet granulation (i.e. using water, a binder such as a silica suspension), extrusion or preferably dry compaction.
[0079] The precipitated silica obtainable by this agglomeration process is generally in the form of granules.
[0080] The precipitated silicas of the invention can be used in many applications, such as catalysts, catalyst supports, absorbents for active substances, in particular carriers for liquids used in foods, such as vitamins (vitamin E or choline chloride), or as viscosity modifiers, antiblocking or anticaking agents, or as additives for toothpaste, concrete or paper. They can also be advantageously used in the manufacture of thermal insulation materials or in the preparation of resorcinol-formaldehyde / silica composites. The precipitated silicas of the invention find a particularly advantageous application as fillers in polymeric compositions.
[0081] Further objects of the present invention are therefore (i) the use of the silica of the present invention as defined above for the preparation of a filled polymer composition, and (ii) a composition comprising the silica of the present invention as defined above and at least one polymer. The term "at least one" when referring to the polymers in the composition is used herein to indicate that one or more polymers of each type may be present in the composition.
[0082] The expression "copolymer" is used herein to refer to a polymer that contains repeat units derived from at least two monomeric units of different nature.
[0083] The at least one polymer may be chosen from thermosetting and thermoplastic polymers, the latter being preferred.
[0084] Notable non-limiting examples of suitable thermoplastic polymers include polystyrene, styrenic polymers such as (meth)acrylic acid ester / styrene copolymers, acrylonitrile / styrene copolymers, styrene / maleic anhydride copolymers, ABS, and the like; acrylic polymers such as polymethyl methacrylate, polycarbonates, polyamides, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyphenylene ethers, polysulfones, polyaryletherketones, polyphenylene sulfides, thermoplastic polyurethanes, polyethylene, polypropylene, polybutene, poly-4-methylpentene, polyolefins such as ethylene / propylene copolymers, ethylene / α-olefin copolymers, copolymers of α-olefins with various monomers, for example ethylene / vinyl acetate copolymers, ethylene / (meth)acrylic acid ester copolymers, ethylene / maleic anhydride copolymers, ethylene / acrylic acid copolymers, polylactic acid, polycaprolactones, and aliphatic polyesters such as aliphatic glycol / aliphatic dicarboxylic acid copolymers.
[0085] The silica of the invention can be advantageously used as a reinforcing filler in elastomer compositions.A preferred object of the invention is therefore a composition comprising the silica of the invention and one or more elastomers, preferably exhibiting at least one glass transition temperature between -150°C and +300°C, for example between -150°C and +20°C.
[0086] Notable non-limiting examples of suitable elastomers are diene elastomers. For example, elastomers derived from aliphatic or aromatic monomers containing at least one unsaturation, such as ethylene, propylene, butadiene, isoprene, styrene, acrylonitrile, isobutylene or vinyl acetate, polybutyl acrylate or mixtures thereof, among others, may be used. Mention may also be made of functionalized elastomers, which are elastomers functionalized by chemical groups located along the polymer chain and / or at one or more ends thereof (e.g., by functional groups capable of reacting with the surface of silica), and halogenated polymers. Mention may be made of polyamides, ethylene homo- and copolymers, propylene homo- and copolymers. Other suitable elastomers are those containing chloro- or bromo-butyl monomers, such as bromo-butylene.
[0087] Among the diene elastomers, mention may be made, for example, of polybutadiene (BR), polyisoprene (IR), butadiene copolymers, isoprene copolymers or mixtures thereof, in particular styrene / butadiene copolymers (SBR, in particular ESBR (emulsion) or SSBR (solution)), isoprene / butadiene copolymers (BIR), isoprene / styrene copolymers (SIR), isoprene / butadiene / styrene copolymers (SBIR), ethylene / propylene / diene terpolymers (EPDM), and also related functionalized polymers (those exhibiting pendant polar groups or reactive or polar groups at the chain ends, for example capable of interacting or reacting with silica).
[0088] Mention may also be made of natural rubber (NR) and epoxidized natural rubber (ENR).
[0089] The polymeric compositions may be sulfur vulcanized or crosslinked, among others, with peroxides or other crosslinking systems such as diamines or phenolic resins.
[0090] In some embodiments, the polymer composition further comprises at least one (silica / polymer) coupling agent and / or at least one coating agent, which may also contain other additives, such as antioxidants.
[0091] Non-limiting examples of suitable coupling agents are, for example, "symmetric" or "asymmetric" silane polysulfides. More specifically, bis((C1-C4)alkoxyl(C1-C4)alkylsilyl(C1-C4)alkyl) polysulfides (especially disulfides, trisulfides or tetrasulfides), such as bis(3-(trimethoxysilyl)propyl) polysulfide or bis(3-(triethoxysilyl)propyl) polysulfide, such as triethoxysilylpropyl tetrasulfide, may be mentioned. Monoethoxydimethylsilylpropyl tetrasulfide may also be mentioned. Silanes containing masked or free thiol functions (such as NXT™ or NXT™ Z45 silane), mercaptopropyltriethoxysilane, and mixed mercaptopropyltriethoxysilane+octyltriethoxysilane (such as SI 363™ from Evonik) may also be mentioned.
[0092] The coupling agent can be pre-grafted to the polymer. It can also be used in the free state (i.e. not pre-grafted) or grafted to the surface of the silica. The same applies to the optional coating agent. If the coupling agent is added to the silica after drying (i.e. grafted), it is usually an ethoxy- or chloro-silane.
[0093] The coupling agent may optionally be combined with a suitable "coupling activator", ie a compound that is mixed with the coupling agent to increase the effectiveness of the latter.
[0094] The weight ratio of the silica of the invention in the polymer composition can vary within a fairly wide range. It usually corresponds to 1% to 250%, in particular 5% to 200%, in particular 10% to 170%, for example 20% to 140%, or even 25% to 130%, or even 10% to 40%, relative to the amount of polymer. In the case of elastomeric compositions, the percentage is therefore sometimes called phr or Per Hundred Rubber.
[0095] The silica according to the invention may advantageously constitute all of the reinforcing inorganic filler and even all of the reinforcing filler of the polymer composition.
[0096] The silica of the invention can optionally be combined with at least one other reinforcing filler, for example a conventional or highly disperse silica such as Zeosil® Premium SW, Zeosil® Premium 200MP, Zeosil® 1165MP, Zeosil® 1115MP or Zeosil® 1085GR (available from Solvay), or another reinforcing filler such as nanoclay or alumina. Alternatively, the silica of the invention can be combined with an organic reinforcing filler such as carbon black nanotubes, graphene, starch, cellulose, etc.
[0097] In that case, the silica according to the invention preferably constitutes at least 30% by weight, preferably at least 60% by weight and even at least 80% by weight of the total amount of reinforcing fillers.
[0098] Further optional components of the formulation include accelerators (such as CBS, MBTS, TBzTD, and DPG), crosslinkers (such as peroxides or sulfur), processing oils, resins (such as terpenes and C 5These include resins, particularly those commercialized as Wingtack™ or Dercolyte™, oligomers of SBR, BR, or IR, activators (such as stearic acid and / or zinc oxide), processing aids (such as fatty acids, zinc soaps, and PEG), waxes (e.g., PE wax) that act as protectants, antioxidants, UV protectants, and antiozonants (such as 6PPD and TMQ).
[0099] The compositions comprising the precipitated silica of the present invention can be used for the manufacture of many articles. The compositions comprising the precipitated silica of the present invention can be used in many articles. Non-limiting examples of finished products comprising at least one of the above polymer compositions are, for example, footwear soles, flooring, gas barriers, flame retardant materials, as well as industrial parts, such as rollers for aerial cables, seals for household appliances, seals for liquid or gas piping, brake system seals, pipes (flexible), sheaths (especially cable sheaths), cables, engine supports, battery separators, conveyor belts, transmission belts, or parts of tires, such as tire treads, the latter being preferred. However, many embodiments of the present invention relate to finished products other than any part of a tire, any finished product other than a tire, and any finished product other than any article including a tire, said finished products consisting of or comprising at least a portion consisting of a composition comprising (i) the precipitated silica of the present invention and (ii) at least one polymer, and optionally one or more elastomers. The finished product other than any part of a tire, any finished product other than a tire, and any finished product other than an article comprising a tire may be selected from the group consisting of footwear soles, flooring, engineering parts (such as rollers for aerial cables), seals (such as seals for household appliances, seals for liquid or gas piping, and brake system seals), pipes (especially flexible pipes), sheaths (especially cable sheaths), cables, supports (especially engine supports), separators (especially battery separators), and belts (such as conveyor belts and transmission belts).
[0100] As indicated above, the precipitated silica of the present invention is present in an amount W of less than 0.50% by weight, preferably less than 0.45% by weight, typically at least 0.01% by weight and less than 0.50% by weight, preferably at least 0.01% by weight and less than 0.45% by weight. Al The specific preferred range of aluminum is W Al is from 0.01% by weight to less than 0.25% by weight (particularly from 0.05% by weight to less than 0.25% by weight) and from 0.25% by weight to less than 0.50% by weight (particularly from 0.25% by weight to less than 0.45% by weight).
[0101] Amount W less than 0.50% by weight Al The precipitated silica of the invention containing aluminum of less than 0.50% by weight can be used in any of the above mentioned applications. Al The precipitated silicas of the invention containing aluminum of 0.50% by weight or less can be advantageously used as fillers in polymer compositions, in particular as reinforcing fillers in elastomeric compositions. It is therefore a preferred object of the invention to provide a method for the preparation of precipitated silicas containing aluminum of 0.50% by weight or less. Al and at least one polymer, in particular in an amount W of less than 0.50% by weight. Al The present invention relates to a composition comprising the precipitated silica of the present invention containing aluminum of 0.50% by weight and one or more elastomers. The nature of the at least one polymer, in particular the nature of the elastomer, may be as detailed above. The composition may further comprise at least one (silica / polymer) coupling agent and / or at least one coating agent, and may also comprise one or more other additives, as also detailed above. The amount W of less than 0.50% by weight in the polymer composition, in particular in the elastomeric composition, may be less than 0.50% by weight. Al The weight proportions of the precipitated silica of the invention containing aluminium may be as detailed above.
[0102] Amount W less than 0.50% by weight Al The precipitated silica of the present invention containing aluminum of less than 0.50% by weight may be used in the manufacture of any one of the specific articles described above. AlThe precipitated silica of the present invention containing aluminum of less than 0.50% by weight W may be used in any of the above specific articles. Al A preferred use of the precipitated silica of the invention containing aluminum in an amount W of less than 0.50% by weight is for the manufacture of one or more parts of a tire, for example the manufacture of a tire tread. Another preferred application thereof is a part or parts of a tire, for example the tire tread. Thus, a preferred object of the invention is to (i) incorporate aluminum in an amount W of less than 0.50% by weight. Al and (ii) at least one polymer, in particular (i) aluminium in an amount W of less than 0.50% by weight. Al and (ii) one or more elastomers. A further preferred object of the present invention is to provide a tire comprising a composition comprising the precipitated silica of the present invention, the composition comprising (i) aluminum in an amount W of less than 0.50% by weight. Al and (ii) at least one polymer. Al and (ii) one or more elastomers. A related object of the present invention is a tire comprising this portion, in particular a tire comprising this tread, and another related object of the present invention is an article comprising a tire comprising this portion, generally a vehicle, in particular an automobile (e.g. a car, van, mobile home, bus, coach, truck or construction equipment such as backhoe loaders or dumpers), but also possibly a non-automotive vehicle (such as a trailer or cart). The nature of the at least one polymer, in particular the nature of the elastomer, may be as detailed above. The composition may additionally comprise at least one (silica / polymer) coupling agent and / or at least one coating agent, and may also comprise one or more other additives, as also detailed above. Aluminum may be present in an amount W of less than 0.50% by weight. Al The proportion by weight of the precipitated silica of the invention, comprising:
[0103] As also indicated above, the precipitated silica of the present invention is instead present in an amount W of at least 0.50% by weight, typically up to 3.00% by weight. Al Aluminum may be included in the specific suitable aluminum range W Al is in the range of 0.50% by weight to 1.50% by weight (particularly, 0.50% by weight to 1.00% by weight), and more than 1.50% by weight to 3.00% by weight.
[0104] An amount W of at least 0.50% by weight Al The precipitated silicas of the invention containing aluminum of at least 0.50% by weight can be used as catalysts, catalyst supports, absorbents for active substances (especially carriers for liquids such as oligomers and process oils), or as viscosity modifiers, texturizing agents, or anti-caking agents, or as additives for concrete or paper. Al The precipitated silica of the present invention containing aluminum of at least 0.50% by weight can also be used for the manufacture of thermal insulation materials or for the preparation of resorcinol-formaldehyde / silica composite materials. Al The precipitated silicas of the invention containing aluminium can also be used as fillers in polymer compositions.
[0105] An amount W of at least 0.50% by weight Al The precipitated silica of the present invention containing aluminum of at least 0.50% by weight may be used to manufacture finished products other than parts of tires, finished products other than tires, and finished products other than articles containing tires, which may contain at least one of the polymer compositions described above. Al The precipitated silica of the invention containing aluminum of less than 0.50% by weight W can be used in finished products other than any part of a tire, finished products other than tires, and finished products other than articles containing tires, which may contain at least one of the polymer compositions described above. Thus, an object of the invention is a finished product other than any part of a tire, any finished product other than tires, and any finished product other than articles containing tires, said finished products containing (i) aluminum in an amount W of less than 0.50% by weight W Aland (ii) at least one polymer, and optionally at least one elastomer. The finished product other than any part of a tire, any finished product other than a tire, and any finished product other than an article comprising a tire may be selected from the group consisting of footwear soles, flooring, engineering parts (such as rollers for aerial cables), seals (such as seals for household appliances, seals for liquid or gas piping, and brake system seals), pipes (particularly flexible pipes), sheaths (particularly cable sheaths), cables, supports (particularly engine supports), separators (particularly battery separators), and belts (such as conveyor belts and transmission belts). The nature of the at least one polymer, and optionally the nature of the elastomer, may be as detailed above. The composition may additionally comprise at least one (silica / polymer) coupling agent and / or at least one coating agent, and may also comprise one or more other additives as also detailed above. An amount W of at least 0.50% by weight of the polymer composition (optionally the elastomeric composition) contained in the finished product other than any part of a tire, any finished product other than a tire, and any finished product other than an article comprising a tire may be selected from the group consisting of footwear soles, flooring, engineering parts (such as rollers for aerial cables), seals (such as seals for household appliances, seals for liquid or gas piping, and brake system seals), pipes (particularly flexible pipes), sheaths (particularly cable sheaths), cables, supports (particularly engine supports), separators (particularly battery separators), and belts (such as conveyor belts and transmission belts). Al The weight proportions of the precipitated silica of the invention containing aluminium may be as detailed above.
[0106] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements in this application to the extent that any term may be unclear, the statements herein shall control. EXAMPLES
[0107] Analysis method The physicochemical properties of the precipitated silica of the invention were determined using the methods described below.
[0108] Possible pretreatment of precipitated silica. When the precipitated silica is in the form of highly aggregated particles, typically when the precipitated silica is in a form other than a powder, it may be desirable to pre-treat it before applying certain analytical methods, such as the method for determining the CTAB surface area and / or the method for determining the primary particle size by SAXS (both relevant methods are detailed below).
[0109] In particular, if, on the one hand, the precipitated silica is in the form of micropearls, i.e. in the primary form of highly aggregated particles, it is advisable to deagglomerate the micropearls to obtain a precipitated silica sample in powder form, before applying the method for determining the primary particle size by SAXS.
[0110] On the other hand, if the precipitated silica is in the form of granules, i.e. highly aggregated particles, it is advisable to deagglomerate the granules to obtain a precipitated silica sample in powder form before applying the method for determining the primary particle size by SAXS, and also before applying the method for measuring the CTAB surface area.
[0111] In both cases the same deagglomeration pretreatment was applied, which is detailed below.
[0112] Deagglomeration pretreatment of highly agglomerated particles, especially precipitated silica in the form of micropearls or granules Highly aggregated particles, especially precipitated silica samples in the form of granules or micropearls, were ground smoothly using a hand-sized agate mortar and hand-sized agate pestle by applying gentle pressure and friction to the silica samples manually to break down the aggregates and other lumps contained therein. Grinding was carried out for a time sufficient for the samples to acquire a visually uniform powder consistency. This time was usually several tens of seconds and did not usually exceed one minute.
[0113] For the sake of clarity, the above pretreatment should not be carried out if the precipitated silica is in powder form. The above pretreatment is carried out according to the methods for determining the BET surface area, the method for determining the fine particle fraction by "Sedigraph", the method for determining the aluminum content W AlWhen the method for determining the CTAB surface area is applied to precipitated silica in the form of micropearls, the pretreatment described above can also be carried out, but is not necessary and therefore will not normally be carried out, when the method for determining the CTAB surface area is applied to precipitated silica in the form of micropearls.
[0114] Determination of CTAB surface area CTAB surface area (S CTAB ) values were determined according to an in-house method based on standard NF ISO5794-1, Annex G. The method was based on the adsorption of CTAB (N-hexadecyl-N,N,N-trimethylammonium bromide) on the "external" surface of the silica.
[0115] In this method, CTAB was adsorbed onto silica with magnetic stirring. Afterwards, the silica and the residual CTAB solution were separated. The excess of unadsorbed CTAB was determined by back titration with sodium bis(2-ethylhexyl)sulfosuccinate (hereafter "AOT") using a titrator. The end point was given by the maximum turbidity of the solution and was determined using an optrode.
[0116] Device Metrohm Optrode (wavelength: 520 nm) connected to a Metrohm Photometer 662; Metrohm titrator: Titrino DMS 716; Metrohm titration software: Tiamo.
[0117] Glass beakers (2000 mL); volumetric flasks (2000 mL); sealable glass bottles (1000 mL and 2000 mL); disposable beakers (100 mL); micropipettes (500 - 5000 μL); magnetic stir bar with 25 mm disk end for adsorption (Ref VWR442-9431); magnetic stir bar for titration (straight); polycarbonate centrifuge tubes (at least 20 mL); centrifuge (capable of a speed of 10000 rpm); glass vials (30 mL); thermobalance.
[0118] Preparation of solutions Preparation of a 5.5 g / L CTAB solution (buffered to approximately pH 9.6): In a 2000 mL beaker containing approximately 1000 mL of distilled water at 25 °C, 54.25 g of boric acid solution ([c] = 4%), 2.60 g of KCl, and 25.8 mL (± 0.1 mL) of sodium hydroxide were added. The solution thus obtained was stirred for 15 minutes, after which 11.00 g ± 0.01 g of CTAB powder (purity 99.9%, purchased from Merck) was added. After stirring, the solution was transferred to a 2000 mL volumetric flask kept at 25 °C and the volume was made up to 2000 mL with distilled water. The solution was transferred to a 2000 mL glass bottle. To avoid crystallization of CTAB (which occurs at 20 °C), the solution was kept at a temperature above 22 °C.
[0119] Preparation of AOT solution: Approximately 1200 mL of distilled water in a 2000 mL beaker was heated to 35° C. with magnetic stirring. 3.7038 g of AOT (98% purity, purchased from Aldrich) was added. The solution was transferred to a 2000 mL volumetric flask and cooled to 25° C. The volume was made up to 2000 mL with distilled water and the solution was transferred to two 1000 mL glass bottles and stored in the dark at 25° C.
[0120] All equipment and solutions were kept at 25° C. throughout the analysis.
[0121] Procedures at the start and end of each experiment Start of experiment: Stir the solution before use. Purge the dosing apparatus before use. Pass at least 40 mL of AOT through the apparatus to ensure it is clean and all air bubbles are removed. End of experiment: Purge the dosing apparatus to remove the AOT solution. Clean the optrode. Soak the optrode in distilled water.
[0122] Determination of blank factor Changes in the concentrations of the AOT and CTAB solutions over time are corrected by the daily determination of a "blank factor" called the ratio R1 = V1 / m1.
[0123] Accurately weigh 4.9000 g ± 0.0100 g of 5.5 g / L CTAB solution (M1) into a 100 mL disposable beaker. Taring the beaker and adding 23.0000 g ± 1.0000 g of distilled water (M1). WATER ) was added accurately. The solution was stirred at 500 rpm using a magnetic stirrer on the addition apparatus and the titration was started. The stirring speed should be strictly constant during the titration without much air bubbles being generated.
[0124] V1 is the end volume of AOT solution needed to titrate m1 of the CTAB solution.
[0125] R1 determinations are made at least twice. If the standard deviation of R1=V1 / m1 exceeds 0.010, the titration is repeated until the standard deviation is less than or equal to 0.010. The daily ratio R1 is calculated as the average of two or three measurements. Note: After each measurement the optrode must be washed with distilled water and dried with absorbent paper.
[0126] Adsorption of CTAB on silica The moisture content (%H 2 O) was measured using a thermobalance (temperature: 160 °C) before the adsorption step as follows: tare the balance with an aluminum cup, weigh out approximately 2 g of silica, spread the powder evenly in the cup, close the balance, and record the moisture content.
[0127] Accurately weigh 0.0100 g of silica (m0) into a 100 mL disposable beaker. 50.0000 mL + 1.0000 mL of CTAB stock solution (V0) was added. The total mass was recorded. The suspension was stirred at 450 rpm on a stir plate using a magnetic stir bar with disk ends for 40 minutes ± 1 minute. After 40 minutes, the sample was removed from the stir plate.
[0128] 25-50 mL of the suspension was transferred to a centrifuge tube (volume depends on the size of the centrifuge tube) and centrifuged at 25 °C for 35 min at a speed of 10,000 rpm. After centrifugation, the tube was gently removed from the centrifuge so as not to disturb the silica. 10-20 mL of the CTAB solution was transferred to a glass vial, which was then stoppered and kept at 25 °C.
[0129] Titration of CTAB solution 4.0000 g ± 0.0100 g of CTAB solution of unknown concentration (m2) was accurately weighed into a 100 mL disposable beaker.
[0130] Set the tare and add 19.4000g ± 1.0000g of distilled water (M water The solution was stirred at 500 rpm on the addition apparatus, and titration with the AOT solution was started.
[0131] V2 is the end volume of AOT required to titrate m2 of the CTAB solution.
[0132] CTAB surface area S CTAB is calculated as follows:
number
[0133] BET surface area determination BET surface area S BET was determined according to the Brunauer-Emmett-Teller method detailed in standard NF ISO 5794-1 Annex E (June 2010) with the following adjustment: the sample was pre-dried at 160°C ± 10°C and the partial pressure P / P used for the measurement 0 was in the range of 0.05 to 0.2.
[0134] Determination of particle size distribution and particle size by centrifugal sedimentation in a disc centrifuge using a centrifugal photosedimentometer (CPS) By centrifugal sedimentation in a disk centrifuge using a centrifugal photosedimentometer, model "CPS DC 24000UHR", marketed by CPS Instruments, d 50 , d 16 , d 84 , FWHM, and L d The instrument is equipped with operating software supplied with the device (operating software version 11g).
[0135] Instrumentation used: For the measurement requirements, the following materials and products were used: Ultrasonic equipment: 1500W generator type Sonics Vibracell VC1500 / VCX1500 with 19mm probe (Converter: CV154 + Booster (Part number: BHNVC21) + 19mm probe (Part number: 630-0208)).
[0136] Analytical balance with 0.1 mg accuracy (e.g. Mettler AE260); Syringes: 1.0 ml and 2.0 ml with 20 ga needle; 50 mL glass beaker with tall profile (SCHOTT DURAN: diameter 38 mm, height 78 mm); Magnetic stirrer with 2 cm stirring bar; Container for ice bath during sonication.
[0137] Chemicals: deionized water; ethanol 96%; sucrose 99%; dodecane, all from Merck; PVC reference standards from CPS Instrument Inc.; the peak maximum of the reference standards used should be between 200 and 600 nm (e.g., 237 nm).
[0138] Preparation of the disc centrifuge For the measurements the following parameters were set: For the calibration standard parameters the information of the PVC standard provided by the supplier was used.
[0139] [Table 1]
[0140] System Configuration The measurement wavelength was set to 405 nm. The following runtime option parameters were set:
[0141] [Table 2]
[0142] All other options in the software were left as set by the instrument manufacturer.
[0143] Preparation of the disc centrifuge Spin the centrifuge disks at 24000 rpm for 30 min. Prepare a density gradient of sucrose (CAS n° 57-50-1) as follows:
[0144] In a 50 mL beaker, prepare a 24% by weight solution of sucrose in water. In a 50 mL beaker, prepare an 8% by weight solution of sucrose in water. After homogenizing these two solutions separately, use a 2 mL syringe to take a sample from each solution and inject it into the rotating disc in the following order: Sample 1: 1.8 mL of 24 wt% solution Sample 2: 1.6 mL of 24 wt% solution + 0.2 mL of 8 wt% solution Sample 3: 1.4 mL of 24 wt% solution + 0.4 mL of 8 wt% solution Sample 4: 1.2 mL of 24 wt% solution + 0.6 mL of 8 wt% solution Sample 5: 1.0 mL of 24 wt% solution + 0.8 mL of 8 wt% solution Sample 6: 0.8 mL of 24 wt% solution + 1.0 mL of 8 wt% solution Sample 7: 0.6 mL of 24 wt% solution + 1.2 mL of 8 wt% solution Sample 8: 0.4 mL of 24 wt% solution + 1.4 mL of 8 wt% solution Sample 9: 0.2 mL of 24 wt% solution + 1.6 mL of 8 wt% solution Sample 10: 1.8 mL of 8 wt% solution.
[0145] Before each injection into the disk, the two solutions are homogenized in the syringe by adding about 0.2 mL of air and then by short manual stirring for a few seconds, without losing any liquid.
[0146] These injections, the total volume of which is 18 mL, aim to create a density gradient that is useful to eliminate certain instabilities that may appear during the injection of the samples to be measured. To protect the density gradient from evaporation, 1 mL of dodecane is added into the rotating disc using a 2 mL syringe. The disc is then left to rotate at 24000 rpm for 60 minutes before any first measurement.
[0147] Sample preparation 3.2 g of silica was weighed into a tall 50 mL glass beaker (SCHOTT DURAN: diameter 38 mm, height 78 mm) and 40 mL of deionized water was added to obtain an 8 wt% suspension of silica. The suspension was stirred with a magnetic stirrer (minimum 20 seconds) before placing the beaker in a crystallizing dish filled with ice and cold water. The magnetic stirrer was removed and the crystallizing dish was placed under an ultrasonic probe placed 1 cm from the bottom of the beaker. The ultrasonic probe was set to 56% of its maximum amplitude and activated for 8 minutes. At the end of the sonication, the beaker was placed again on a magnetic stirrer with a 2 cm magnetic stir bar stirring at a minimum of 500 rpm until after sample extraction.
[0148] The ultrasonic probe must be in good working order. The following tests must be carried out and in case of negative results a new probe must be used: visual inspection of the physical integrity of the end of the probe (roughness depth less than 2 mm measured with fine calipers); 50 must be 93nm ±3nm.
[0149] analysis Before analyzing each sample, a calibration standard was recorded. In each case, 0.1 mL of a PVC standard was injected, provided by CPS Instruments, whose characteristics were entered in advance into the software. It is important to start the measurement in the software simultaneously with this first injection of the PVC standard. The instrument must be verified before injecting 100 μL of pre-sonicated sample by ensuring that the measurement is started simultaneously upon injection.
[0150] These injections were performed with two clean 1 mL syringes.
[0151] At the end of the measurement, when the time required to settle all particles of smaller diameter (configured in the software to be 0.02 μm) is reached, the ratio of each diameter class is obtained. The curve obtained is called the aggregate size distribution.
[0152] result Value d 50 , d 16 , d 84 , and L d is based on the distribution plotted on a straight line. The integration of the particle size distribution function of the diameters makes it possible to obtain the "cumulative" distribution, i.e. the total mass of particles between the minimum diameter and the diameter of interest.
[0153] d 50 is the diameter below and above which 50% of the population is. 50 is referred to as the median size, or diameter, of the silica particles.
[0154] d 84 is the diameter below which 84% of the particle's total mass is measured.
[0155] d 16 is the diameter below which 16% of the particle's total mass is measured.
[0156] L d is the formula: L d =(d 84 -d 16 ) / d 50 It is calculated according to:
[0157] The FWHM is calculated based on the derivative curve of the cumulative distribution described above, as explained herein above.
[0158] Determination of fine particle fraction by the "sedigraph" method. In this test, the ability to disperse silica is measured by particle size measurement (by sedimentation) of a silica suspension previously deagglomerated by ultrasonic treatment. The ultrasonic deagglomeration (or dispersion) is carried out using a VIBRACELL BIOBLOCK ultrasonic device (1500W) equipped with a probe with a diameter of 19 mm. The particle size measurement is carried out using a Sedigraph particle size measuring device (sedimentation in a gravitational field + X-ray beam scanning).
[0159] 6.4 grams of silica are weighed into a tall beaker (volume 100 ml) and made up to 80 grams with permuted water. An 8% aqueous suspension of silica is then produced, which is homogenized by magnetic stirring for 2 minutes. Then ultrasonic deagglomeration (dispersion) is performed as follows: the probe is immersed over a length of 3 cm and the power is adjusted to deliver 58 kJ to the suspension for 480 seconds. Then particle size measurements are performed with a Sedigraph particle size measuring device. Measurements are performed from 85 μm to 0.3 μm at a density of 2.1 g / mL. The deagglomerated silica suspension is circulated in a Sedigraph particle size cell, optionally after pre-cooling. As soon as a particle size of 0.3 μm is reached, the analysis is automatically stopped (approximately 45 min). Then the fine particle fraction (τf), i.e. the proportion (by weight) of particles with a particle size of less than 1 μm, is calculated. The higher this fine particle fraction (τf), i.e. the proportion of particles with a size of less than 1 μm, the better the dispersion of the silica.
[0160] It is understood that the ultrasonic probe should be in proper operating condition. For this purpose, the following checks can be performed: (i) visual inspection of the physical integrity of the end of the probe (roughness depth less than 2 mm measured with fine calipers), and / or (ii) the measured τf value of the commercial silica Zeosil® 1165MP aged for at least 2 years should be 97%. In case of a negative result, the power should be readjusted. If negative results persist, a new probe should be used.
[0161] Determination of primary particle size by SAXS 1) Principle of the method Small angle X-ray scattering (SAXS) consists of the conical deviation of an incident X-ray beam of wavelength λ through a sample, with an angle of a few degrees. The scattering angle θ corresponds to a wave vector defined by the following relation:
number
[0162] Each scattering angle corresponds to a wave vector q defined in reciprocal space. This wave vector corresponds to a spatial scale defined in real space, equal to 2π / q. Thus, scattering at small angles characterizes large distances within the sample, and conversely, scattering at large angles characterizes small distances within the sample. The technique is sensitive to how the material is distributed in space.
[0163] The basic references on this technology are: [1] Small Angle Scattering of X rays, Guinier A., Fournet G., (1955), Wiley, New York. [2] Small Angle X Ray Scattering, Glatter O., Krattky O., (1982), Academic Press, New York. [3]Analysis of the Small-Angle Intensity Scattered by a Porous and Granularmedium,Spalla O.,Lyonnard S.,Testard F.,J.Appl.Cryst.(2003),36,338-347.10
[0164] The requirements for SAXS to characterize silica according to the following criteria are: The SAXS assembly is operated in transmission geometry (i.e. the incident beam passes through the sample) and the incident wavelength is between 0.5 and 2 Angstroms (Å); Wave vector spacing q is 0.015 Å -1 ~0.30Å -1 This allows the determination of real space distances in the range of 420 Å to 20 Å. The assembly is verified on the q-scale using appropriate standards (e.g. silver behenate, octadecanol, or other compounds giving fine SAXS lines falling within the q-interval above); a one-dimensional linear detector, or preferably two-dimensional; The assembly must be capable of measuring the transmittance of the preparation, i.e. the ratio of the intensity transmitted by the sample to the incident intensity.
[0165] Such an assembly may be, for example, a laboratory assembly operating with a source of the X-ray tube type or of the rotating anode type, preferably using copper Kα radiation of 1.54 Å. The detector may be a CCD detector, an image plate or a gas detector. It may also be a SAXS mount on a synchrotron. In the framework of this application, a CCD detector was used.
[0166] 2) Procedure The silica sample is analyzed in powdered solid form. The powder is placed between two windows transparent to X-rays. Separately from this preparation, an empty cell is made, containing no silica inside, but only the two transparent windows. The diffusion through the empty cell is recorded separately from the diffusion of silica. During this operation, called the "background measurement", the scattering intensity comes from all external contributions to the silica, such as electronic background noise, diffusion through the transparent windows, and residual divergence of the incident beam.
[0167] These transparent windows must provide low background noise in front of the intensity scattered by the silica over the wavevector interval to be investigated. They can be constructed of mica, Kapton, or Mylar film, or preferably an adhesive Kapton film or Mylar with a thin layer of grease.
[0168] Prior to the actual SAXS acquisition on the silica, the quality of the preparation must be checked by a transmission measurement of the cell containing the silica.
[0169] So the steps to take are: 2.1) Preparation of a two-window cell containing no silica (empty cell); 2.2) Preparation of a two-window cell (empty cell) containing a sample of silica powder.
[0170] The amount of silica introduced should be less than 50 mg. The silica must form a layer no thicker than 100 µm. It is preferable to obtain a monolayer in which the silica grains are located on the window, but this is easy to obtain with sticky windows. The quality of the preparation is controlled by the measurement of the transmittance (step 2.3).
[0171] 2.3) Measurement of the transmittance of the empty cell and the silica cell. The R ratio is defined as: R = transmittance of silica cell / transmittance of empty cell To maintain a satisfactory signal-to-noise ratio for large q while minimizing the risk of multiple scattering, R should be between 0.85 and 1. If the R value is too low, the amount of silica visible in the beam must be reduced, and if the R value is too high, silica must be added.
[0172] 2.4) SAXS acquisition in an empty cell and a silica cell. The acquisition time is determined so that the signal-to-noise ratio is acceptable for large q values. These are q = 0, 12 Å, -1 In the immediate vicinity of , the fluctuation of the function F(q) defined below should not exceed + / - 5% relative to the value taken by the function F at that point.
[0173] 2.5) When using a 2D detector: each of the two 2D profiles are radially grouped to obtain the scattering intensity as a function of the wave vector q. To determine the scattering intensity, the exposure time, the intensity of the incident beam, the transmittance of the sample and the solid angle intercepted by the detector pixels must be taken into account. In determining the wave vector, the wavelength of the incident beam and the sample-to-detector distance shall be taken into account.
[0174] 2.6) If a one-dimensional detector is used: The previously described determination of scattering intensity and wave vector is made, but no radial grouping is expected.
[0175] 2.7) This gives two profiles (one for the empty cell and one for the silica cell) that provide reduced information on the variation of the scattering intensity as a function of the wavevector q.
[0176] 2.8) Subtraction of the intensity scattered by the empty cell from the intensity scattered by the silica cell ("background" subtraction).
[0177] 2.9) After subtraction of the "background", the SAXS profile of silica decays monotonically according to a law close to Porod's law, i.e., the intensity decays monotonically as q -4 It decreases very rapidly with the wave vector, following a law close to a power law of . This small deviation from the Porod law is best visualized by representing the data according to the so-called Krattky-Porod method. This is the problem of expressing F(q) as a function of q, given by: F(q) = I × q 4 where F represents the SAXS profile according to the Kratty-Porod method, I represents the scattering intensity after subtraction of the “background”, and q is the wave vector (Å -1 )
[0178] 2.10) In the Krattky-Porod representation, when describing the profile, a maximum can sometimes be observed, which is associated with the presence of primary particles of roughly defined size. This maximum is more pronounced the lower the polydispersity. If the primary particles are monodisperse, a second and even a third oscillation is observed to the right of the maximum. The position of the maximum is related to the average particle size of the primary particles by the law 2π / q.
[0179] Two different determinations can be made, both of which provide information about the size of the primary particles.
[0180] The first decision is I×q 4 =F(q) is based on the location of the maximum in 2π / q maxFor a single strip population of spheres, this distance does not correspond exactly to the diameter, but to 115% of the diameter (Å). Its use does not give a size distribution, only an average diameter, with the largest particles having the strongest influence.
[0181] In another determination, the average size d ZS (Zimm Schultz mean diameter) is obtained. Therefore, I×q 4 The SAXS profile of =F(q) is modelled by a distribution of independent spheres (with different diameters) of the Zimm-Schultz distribution type.
[0182] The skilled artisan is familiar with the use of such distributions to fit many distributions observed in various fields of chemistry. References may in particular be made to: ·J. Welch,VA Bloomfield,J.Pol.Sci.,Polymer Physics Edition,vol.11(1973),entitled“Fitting Polymer Distribution Data to a Schulz-Zimm Function” ·HJ Angerman, G.ten Brinke, JJM Slot, The European Physical Journal B,12,397-404 (1999), entitled “Influence of polydispersity on the phase behavior of statistical multiblock copolymers with Schultz-Zimm blockmolecular weight distributions”, and ·LHHanus, HJPloehn, Langmuir, 15, 3091-3100 (1999), entitled “Conversion of Intensity-averaged Photon Correlation Spectroscopy measurements to Number-Averaged Particle Size Distributions.1.Theoretical Development”.
[0183] This last paper concerns the determination of the mean particle size of the particle distribution, as in the case of the silica of the invention. The Zimm-Schultz distribution functions shown in Table 1 of this last paper have been evaluated, and the general formula for converting the intensity-average particle size and the polydispersity index into the mean and standard deviation of the Zimm-Schultz distribution function can be found in Table 2 of this last paper.
[0184] The modeled SAXS profile is based on well-known SAXS form factors, so for a single sphere with diameter d (d=2×r, where r is the radius of the sphere in Å), we obtain:
number
[0185] For a distribution of independent spheres with different diameters, the (total) scattered intensity I(q) after subtracting the "background" at wave vector q is:
number
number
[0186] The Zimm Schultz distribution function of independent spheres f(r)=f ZS (r) is commonly expressed as:
number
number
[0187] Therefore, the modeled SAXS profile F based on independent spheres having a Zimm-Schultz distribution according to the present invention ZS (q) is as follows:
number
[0188] Therefore, to fit the modeled profile, we need to determine: 1) the mean diameter d ZS and 2) polydispersity index i p It requires two inputs: (with parameters t and a) and F on the y-axis. ZS A multiplicative constant k is used to adjust the profile.
[0189] These inputs are F(q)=Iq 4 (SAXS profile in Krattky-Porod representation) is defined as the wave vector interval [q min , q max ] can be determined using conventional numerical tools or based on trial and error (for the avoidance of doubt, -1 q expressed in units min and q max represent the lower and upper bounds of the wave vector interval, respectively). If the modeled and experimental data match as closely as possible in the interval surrounding the maximum (i.e., the experimental and modeled values of F(q) are ZS The best fit will be found when the sum of squared differences of (q) is minimized.
[0190] In practice, the Zimm-Schultz distribution is min , r max For a given wave vector, each class of the discretized Zimm-Schultz distribution is given its shape factor [I(q,r), formula (SF)] and its weight f ZS (r) Modeled SAXS profile F ZS (q) Contribute to:
number
[0191] For convenience, the above formula may be implemented and calculated in a spreadsheet.
[0192] The above model does not take into account agglomeration and therefore the presence of correlation between the spheres. It also does not take into account coalescence, i.e. the presence of additional material that holds the primary particles together.
[0193] 2.11) From this model, the mean diameter d ZS Determine the SAXS particle size.
[0194] Amount of aluminum W Al Decision SiO 2 The weight of aluminum based on the weight of the sample was measured using XRF wavelength dispersive X-ray fluorescence spectroscopy using a WDXRF Panalytical instrument. Sample analysis showed that the content of aluminum ranged from 0.1 to 3.0% (by weight) Al / SiO 2 A thin Prolene film (4 μm Chemplex ( 登録商標The experiments were carried out in helium in a 4 cm diameter cell using silica, specifically silica powder, contained in a cell covered with a SiO 2 .
[0195] Al and Si fluorescence were measured using the following parameters: Al Kα angle 2θ = 144.9468° (20 s), background signal angle 2θ = -1.2030° (4 s), Si Kα angle 2θ = 109.1152° (10 s), tube power 4 kW (32 kV, 125 mA), PE002 crystal and 550 μm collimator, gas flux detector.
[0196] Al / SiO exceeding 3.0% 2 The weight of aluminum in precipitated silica samples containing Al was determined by ICP OES (Inductively Coupled Plasma Optical Emission Spectroscopy). The precipitated silica samples were digested in hydrofluoric acid (e.g., about 0.2-0.3 g of precipitated silica in 1 mL of hydrofluoric acid with a concentration of 40%). A clear solution was obtained, which was diluted with 5% aqueous nitric acid according to the expected Al concentration. The intensity measured at the Al-specific wavelength (396.152 nm) was compared with a calibration curve in the range of 0.05-2.00 mg / L obtained using aluminum standards (four standards with the following concentrations: 0.10, 0.20, 1.00, 2.00 mg / L) under similar analytical conditions. The weight content of aluminum in the precipitated silica samples was calculated using the dilution factor. The SiO of the precipitated silica samples was then 2 The weight of aluminum based on the weight of the precipitated silica sample is calculated based on the weight of the precipitated silica sample. 2 The aluminum content was calculated from the weight content of aluminum and the weight content of water in the precipitated silica sample, taking into account that the aluminum content is typically about 95 to about 99% by weight and the water content is typically about 5 to about 1% by weight.
[0197] Determination of moisture content Silica samples, especially those with Al / SiO > 3.0% 2 The moisture content of silica samples containing was determined according to ISO 787-2. Silica volatiles (referred to herein as moisture for simplicity) were determined after drying at 105° C. for 2 hours. The loss on drying consisted primarily of moisture in nature.
[0198] 10 g of powdered silica, spherical silica (Micropearl), or granular silica were weighed out accurately to 0.1 mg (weighed sample E) and placed in a dry weighing bottle (diameter 8 cm, height 3 cm) with a ground glass lid. With the lid open, the samples were dried at 105 ± 2 °C in a drying cabinet for 2 h. Afterwards, the weighing bottle was closed and cooled to room temperature in a desiccator containing silica gel as a desiccant. Weighed portion A was determined gravimetrically. The moisture content was determined in % according to [(E(g)-A(g))*100%] / (E(g)).
[0199] Examples 1 to 7: Synthesis of Silica Comparative Example 1 (silica obtained according to the method described in WO 03 / 016215 in the name of the Applicant) In a 25 L stainless steel reactor, 15.2 L of normal water and 356 g of Na 2 SO 4 (solid). The resulting solution was stirred and heated to reach 92°C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium. Sulfuric acid (concentration: 7.7% by weight) was charged into the reactor until a pH value of 4.43 was reached.
[0200] Sodium silicate solution (SiO) at a flow rate of 100.7 g / min 2 / Na 2 O weight ratio=3.46;SiO 2 A solution of sodium silicate with a flow rate of 108 g / min and a 7.7% by weight solution of sulfuric acid with a flow rate of 122.6 g / min were then simultaneously introduced in 14.3 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was at a value of 4.43. During this step, a gel point was observed after 8.7 minutes. At the end of this step, a solution of sodium silicate with a flow rate of 107.2 g / min and a 96% by weight solution of sulfuric acid were simultaneously introduced in 9.9 minutes. The flow rate of the 96% by weight solution of sulfuric acid was adjusted so that the pH of the reaction medium was maintained at a value of 4.05. The silicate added after the gel point represented 64% of the total silicate added since the start of the reaction.
[0201] The introduction of acid was then stopped, while the addition of the sodium silicate solution was maintained at a flow rate of 121 g / min over 2.4 minutes, until the reaction medium reached a pH value of 8.00.
[0202] Then, a sodium silicate solution with a flow rate of 168.7 g / min and a 96% by weight sulfuric acid solution were introduced simultaneously over a period of 18 minutes, the flow rate of the 96% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0203] At the end of this step, the pH of the reaction medium was brought to a value of 4.6 using 96% by weight sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.
[0204] The reaction slurry was filtered and washed using a filter press. 2 The aluminate solution ([Al]: 11.6 wt%, [Na 2 O]: 19.9 wt%) in the form of SiO 2 The resulting cake was mechanically and chemically disintegrated by adding about 0.30% by weight of aluminum metal Al (about 0.03% by weight of Al is understood to come from the silicate solution). The flow rate of the 7.7% by weight sulfuric acid solution was adjusted to maintain the pH of the reaction medium at a value of 6.3. The resulting slurry was dried by a nozzle spray dryer to obtain precipitated silica CS1.
[0205] The properties of the precipitated silica CS1 are reported in Table 1 below.
[0206] Example 2 (according to the present invention) In a 25 L stainless steel reactor, 15.3 L of normal water and 359 g of Na 2 SO 4 (solid). The resulting solution was stirred and heated to reach 92°C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium. Sulfuric acid (concentration: 7.7% by weight) was charged into the reactor until a pH value of 4.25 was reached.
[0207] Sodium silicate solution (SiO ) at a flow rate of 103 g / min. 2 / Na 2 O weight ratio=3.46;SiO 2 A solution of sodium silicate with a concentration of 19.33% by weight was introduced into the reactor over a period of 45 seconds. The same sodium silicate solution was used throughout the process. A solution of sodium silicate with a flow rate of 108 g / min and a solution of 7.7% by weight of sulfuric acid with a flow rate of 122.6 g / min were then introduced simultaneously over a period of 14.53 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was set to a value of 4.25. During this step, a gel point was observed after 8.74 minutes. At the end of this step, a solution of sodium silicate with a flow rate of 107 g / min and a solution of 96% by weight of sulfuric acid were introduced simultaneously over a period of 0.2 minutes. The flow rate of the 96% by weight of sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.25. The silicate added after the gel point represents 41% of the total silicate added since the start of the reaction.
[0208] The introduction of acid was then stopped while the addition of the sodium silicate solution was maintained at a flow rate of 116 g / min over 1.94 minutes, until the reaction medium reached a pH value of 8.00.
[0209] Then, a sodium silicate solution with a flow rate of 169 g / min and a 96% by weight sulfuric acid solution were introduced simultaneously over a period of 18.15 minutes, the flow rate of the 96% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0210] At the end of this step, the pH of the reaction medium was brought to a value of 4.5 using 96% by weight sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.
[0211] The reaction slurry was filtered and washed using a filter press. 2 The aluminate solution ([Al]: 11.6 wt%, [Na 2 O]: 19.9 wt%) in the form of SiO 2The resulting cake was mechanically and chemically disintegrated by adding about 0.30% by weight of aluminum metal Al (about 0.03% by weight of Al is understood to come from the sodium silicate solution). The flow rate of the 7.7% by weight sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 6.3. The resulting slurry was dried by a nozzle spray dryer to obtain precipitated silica S2.
[0212] The characteristics of the precipitated silica S2 are reported in Table 1.
[0213] Example 3 (according to the present invention) In a 25 L stainless steel reactor, 15.24 L of normal water and 356 g of Na 2 SO 4 (solid). The resulting solution was stirred and heated to reach 92° C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium. Sulfuric acid (concentration: 7.7% by weight) was introduced into the reactor until a pH value of 4.55 was reached.
[0214] Sodium silicate solution (SiO 2 / Na 2 O weight ratio=3.47;SiO 2 A solution of sodium silicate with a flow rate of 110 g / min and a 7.7% by weight solution of sulfuric acid with a flow rate of 109.9 g / min were then simultaneously introduced into the reactor over a period of 45 seconds. The same sodium silicate solution was used throughout the process. A solution of sodium silicate with a flow rate of 110 g / min and a solution of 7.7% by weight of sulfuric acid with a flow rate of 109.9 g / min were then simultaneously introduced over a period of 12.45 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was set to a value of 4.55. During this step, a gel point was observed after 7 minutes. At the end of this step, a solution of sodium silicate with a flow rate of 107.2 g / min and a solution of 96% by weight of sulfuric acid were simultaneously introduced over a period of 0.05 minutes. The flow rate of the 96% by weight solution of sulfuric acid was adjusted so that the pH of the reaction medium was maintained at a value of 4.55. The silicate added after the gel point represented 44% of the total silicate added since the start of the reaction.
[0215] The introduction of acid was then stopped while the addition of the sodium silicate solution was maintained at a flow rate of 116.6 g / min over 1.45 minutes until the reaction medium reached a pH value of 8.00.
[0216] Then, a sodium silicate solution with a flow rate of 159.4 g / min and a 96% by weight sulfuric acid solution were introduced simultaneously over a period of 21.95 minutes, the flow rate of the 96% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0217] At the end of this step, the pH of the reaction medium was brought to a value of 4.55 using 96% by weight sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.
[0218] The reaction slurry was filtered and washed using a filter press. 2 The aluminate solution ([Al]: 11.6 wt%, [Na 2 O]: 19.9 wt%) in the form of SiO 2 The resulting cake was mechanically and chemically disintegrated by adding about 0.30% by weight of aluminum metal Al (about 0.03% by weight of Al is understood to come from the sodium silicate solution). The flow rate of the 7.7% by weight sulfuric acid solution was adjusted to maintain the pH of the reaction medium at a value of 6.3. The resulting slurry was dried by a nozzle spray dryer to obtain precipitated silica S3.
[0219] The characteristics of the precipitated silica S3 are reported in Table 1.
[0220] Example 4 (according to the present invention) In a 25 L stainless steel reactor, 15.3 L of normal water and 359 g of Na 2 SO 4 (solid). The resulting solution was stirred and heated to reach 92° C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium. Sulfuric acid (concentration: 7.7% by weight) was introduced into the reactor until a pH value of 4.05 was reached.
[0221] Sodium silicate solution (SiO) at a flow rate of 101.4 g / min 2 / Na 2 O weight ratio=3.46;SiO 2 A solution of sodium silicate with a flow rate of 109.3 g / min and a 7.7 wt. % sulfuric acid solution with a flow rate of 124.8 g / min were then simultaneously introduced in 13.6 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was set to a value of 4.05. During this step, a gel point was observed after 10 minutes. At the end of this step, a solution of sodium silicate with a flow rate of 107.2 g / min and a 96 wt. % sulfuric acid solution were simultaneously introduced in 0.2 minutes. The flow rate of the 96 wt. % sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.05. The silicate added after the gel point represents 28% of the total silicate added since the start of the reaction.
[0222] The introduction of acid was then stopped while the addition of the sodium silicate solution was maintained at a flow rate of 147.6 g / min over 1.2 minutes until the reaction medium reached a pH value of 8.00.
[0223] Then, a sodium silicate solution with a flow rate of 168.6 g / min and a 96% by weight sulfuric acid solution were simultaneously introduced over a period of 18.12 minutes, the flow rate of the 96% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0224] At the end of this step, the pH of the reaction medium was brought to a value of 4.6 using 96% by weight sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.
[0225] The reaction slurry was filtered and washed using a filter press. 2 The aluminate solution ([Al]: 11.6 wt%, [Na 2 O]: 19.9 wt%) in the form of SiO 2The resulting cake was mechanically and chemically disintegrated by adding about 0.30% by weight of aluminum metal Al (about 0.03% by weight of Al is understood to come from the sodium silicate solution). The flow rate of the 7.7% by weight sulfuric acid solution was adjusted to maintain the pH of the reaction medium at a value of 6.3. The resulting slurry was dried by a nozzle spray dryer to obtain precipitated silica S4.
[0226] The characteristics of the precipitated silica S4 are reported in Table 1.
[0227] Example 5 (according to the present invention) In a 25 L stainless steel reactor, 15.3 L of normal water and 359 g of Na 2 SO 4 (solid). The resulting solution was stirred and heated to reach 92°C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium. Sulfuric acid (concentration: 7.7% by weight) was introduced into the reactor until a pH value of 4.00 was reached.
[0228] Sodium silicate solution (SiO 2 / Na 2 O weight ratio=3.46;SiO 2 A solution of sodium silicate with a flow rate of 108.9 g / min and a 7.7 wt. % sulfuric acid solution with a flow rate of 126.4 g / min were then simultaneously introduced in 13.3 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was set to a value of 4.00. During this step, a gel point was observed after 11 minutes. At the end of this step, a solution of sodium silicate with a flow rate of 107.2 g / min and a 96 wt. % sulfuric acid solution were simultaneously introduced in 0.02 minutes. The flow rate of the 96 wt. % sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.00. The silicate added after the gel point represents 17% of the total silicate added since the start of the reaction.
[0229] The introduction of acid was then stopped while the addition of the sodium silicate solution was maintained at a flow rate of 131.1 g / min over 1.52 minutes, until the reaction medium reached a pH value of 8.00.
[0230] Then, a sodium silicate solution with a flow rate of 161.6 g / min and a 96% by weight sulfuric acid solution were introduced simultaneously over a period of 26.52 minutes, the flow rate of the 96% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0231] At the end of this step, the pH of the reaction medium was brought to a value of 4.6 using 96% by weight sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.
[0232] The reaction slurry was filtered and washed using a filter press. 2 The aluminate solution ([Al]: 11.6 wt%, [Na 2 O]: 19.9 wt%) in the form of SiO 2 The resulting cake was mechanically and chemically disintegrated by adding about 0.30% by weight of aluminum metal Al (about 0.03% by weight of Al is understood to come from the silicate solution). The flow rate of the 7.7% by weight sulfuric acid solution was adjusted to maintain the pH of the reaction medium at a value of 6.3. The resulting slurry was dried by a nozzle spray dryer to obtain precipitated silica S5.
[0233] The properties of the precipitated silica S5 are reported in Table 1 below.
[0234] Example 6 (according to the present invention) In a 25 L stainless steel reactor, 15.3 L of normal water and 359 g of Na 2 SO 4 (solid). The resulting solution was stirred and heated to reach 92° C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium. Sulfuric acid (concentration: 7.7% by weight) was introduced into the reactor until a pH value of 4.05 was reached.
[0235] Sodium silicate solution (SiO 2 / Na 2 O weight ratio=3.46;SiO 2 A solution of sodium silicate with a flow rate of 105.9 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 125.6 g / min were then simultaneously introduced into the reactor over a period of 45 seconds. The same sodium silicate solution was used throughout the process. A solution of sodium silicate with a flow rate of 105.9 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 125.6 g / min were then simultaneously introduced over a period of 13.35 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was set to a value of 4.05. During this step, a gel point was observed after 12 minutes. At the end of this step, a solution of sodium silicate with a flow rate of 101.9 g / min and a 96% by weight sulfuric acid solution were simultaneously introduced over a period of 3.82 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.05. The silicate added after the gel point represents 30% of the total silicate added since the start of the reaction.
[0236] The introduction of acid was then stopped while the addition of the sodium silicate solution was maintained at a flow rate of 111.9 g / min over a period of 2.18 minutes, until the reaction medium reached a pH value of 8.00.
[0237] Then, a sodium silicate solution with a flow rate of 164.7 g / min and a 96% by weight sulfuric acid solution were introduced simultaneously over a period of 22.52 minutes, the flow rate of the 96% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0238] At the end of this step, the pH of the reaction medium was brought to a value of 4.6 using 96% by weight sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.
[0239] The reaction slurry was filtered and washed using a filter press. 2 The aluminate solution ([Al]: 11.6 wt%, [Na 2 O]: 19.9 wt%) in the form of SiO 2The resulting cake was mechanically and chemically disintegrated by adding about 0.30% by weight of aluminum metal Al (about 0.03% by weight of Al is understood to come from the sodium silicate solution). The flow rate of the 7.7% by weight sulfuric acid solution was adjusted to maintain the pH of the reaction medium at a value of 6.3. The resulting slurry was dried by a nozzle spray dryer to obtain precipitated silica S6.
[0240] The properties of the precipitated silica S6 are reported in Table 1 below.
[0241] Example 7 (according to the invention) In a 25 L stainless steel reactor, 15.3 L of normal water and 359 g of Na 2 SO 4 (solid). The resulting solution was stirred and heated to reach 92° C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium. Sulfuric acid (concentration: 7.7% by weight) was introduced into the reactor until a pH value of 4.05 was reached.
[0242] Sodium silicate solution (SiO 2 / Na 2 O weight ratio=3.46;SiO 2 A solution of sodium silicate with a flow rate of 105.5 g / min and a 7.7% by weight solution of sulfuric acid with a flow rate of 125.3 g / min were then simultaneously introduced in 13.35 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was set to a value of 4.05. During this step, a gel point was observed after 11 minutes. At the end of this step, a solution of sodium silicate with a flow rate of 105.9 g / min and a 96% by weight solution of sulfuric acid were simultaneously introduced in 0.02 minutes. The flow rate of the 96% by weight solution of sulfuric acid was adjusted so that the pH of the reaction medium was maintained at a value of 4.05. The silicate added after the gel point represents 18% of the total silicate added since the start of the reaction.
[0243] The introduction of acid was then stopped, while the addition of the sodium silicate solution was maintained at a flow rate of 181.9 g / min over 0.85 min, until the reaction medium reached a pH value of 8.00.
[0244] Then, a sodium silicate solution with a flow rate of 169.3 g / min and a 96% by weight sulfuric acid solution were introduced simultaneously over a period of 22.50 minutes, the flow rate of the 96% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0245] At the end of this step, the pH of the reaction medium was brought to a value of 4.6 using 96% by weight sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.
[0246] The reaction slurry was filtered and washed using a filter press. 2 The aluminate solution ([Al]: 11.6 wt%, [Na 2 O]: 19.9 wt%) in the form of SiO 2 The resulting cake was mechanically and chemically disintegrated by adding about 0.30% by weight of aluminum metal Al (about 0.03% by weight of Al is understood to come from the sodium silicate solution). The flow rate of the 7.7% by weight sulfuric acid solution was adjusted to maintain the pH of the reaction medium at a value of 6.3. The resulting slurry was dried by a nozzle spray dryer to obtain precipitated silica S7.
[0247] The properties of the precipitated silica S7 are reported in Table 1 below.
[0248] Example 8 (according to the present invention) In a 25 L stainless steel reactor, 15.3 L of normal water and 359 g of Na 2 SO 4 (solid). The resulting solution was stirred and heated to reach 92° C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium. Sulfuric acid (concentration: 7.7% by weight) was introduced into the reactor until a pH value of 4.25 was reached.
[0249] Sodium silicate solution (SiO 2 / Na 2 O weight ratio=3.46;SiO 2 A solution of sodium silicate with a flow rate of 140.7 g / min and a 7.7 wt. % sulfuric acid solution with a flow rate of 159.2 g / min were then simultaneously introduced in 11.72 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was set to a value of 4.25. During this step, a gel point was observed after 8 minutes. At the end of this step, a solution of sodium silicate with a flow rate of 113.8 g / min and a 96 wt. % sulfuric acid solution were simultaneously introduced in 5.05 minutes. The flow rate of the 96 wt. % sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.55. The silicate added after the gel point represents 36% of the total silicate added since the start of the reaction.
[0250] The introduction of acid was then stopped, while the addition of the sodium silicate solution was maintained at a flow rate of 229.7 g / min over 0.6 min, until the reaction medium reached a pH value of 8.00.
[0251] Then, a sodium silicate solution with a flow rate of 167.6 g / min and a 96% by weight sulfuric acid solution were introduced simultaneously over a period of 18.10 minutes, the flow rate of the 96% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0252] At the end of this step, the pH of the reaction medium was brought to a value of 4.58 using 96% by weight sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained. The reaction slurry was filtered and washed with a filter press. Approximately 0.33% by weight of Al / SiO 2 The aluminate solution ([Al]: 11.6 wt%, [Na 2 O]: 19.9 wt%) in the form of SiO 2The resulting cake was mechanically and chemically disintegrated by adding about 0.30% by weight of aluminum metal Al (about 0.03% by weight of Al is understood to come from the sodium silicate solution). The flow rate of the 7.7% by weight sulfuric acid solution was adjusted to maintain the pH of the reaction medium at a value of 6.3. The resulting slurry was dried by a nozzle spray dryer to obtain precipitated silica S8.
[0253] The properties of the precipitated silica S8 are reported in Table 1 below.
[0254] Comparative Example 9 (silica obtained according to the method described in WO 03 / 016215 in the name of the Applicant) In a 25 L stainless steel reactor, 16.0 L of normal water and 245 g of Na 2 SO4 (solid) was charged. The resulting solution was stirred and heated to reach 92°C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium. Sulfuric acid (concentration: 7.7% by weight) was introduced into the reactor until a pH value of 4.10 was reached.
[0255] Aqueous sodium silicate solution (SiO 2 / Na 2 O weight ratio=3.47, SiO 2 A 7.7% by weight aqueous solution of sulfuric acid with a concentration of 19.90% by weight and a flow rate of 119.5 g / min was introduced simultaneously over a period of 15.15 minutes. The flow rate of the sulfuric acid was adjusted so as to maintain the pH of the reaction liquid at 4.10. At the end of this step, a sodium silicate solution with a flow rate of 102.9 g / min and a 96% by weight solution of sulfuric acid were introduced simultaneously over a period of 10.05 minutes. The flow rate of the 96% by weight solution of sulfuric acid was adjusted so as to maintain the pH of the reaction medium at a value of 4.10.
[0256] The introduction of acid was then stopped, while the addition of the sodium silicate solution was maintained at a flow rate of 110.1 g / min over 2.5 minutes, until the reaction medium reached a pH value of 8.00.
[0257] Then, a sodium silicate solution with a flow rate of 163.3 g / min and a 96% by weight sulfuric acid solution were introduced simultaneously over a period of 17.95 minutes, the flow rate of the 96% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0258] At the end of this simultaneous addition, the pH of the reaction medium was brought to a value of 4.6 using 96% by weight sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.
[0259] The reaction slurry was filtered and washed using a filter press. 2 The aluminate solution ([Al]: 11.6 wt%, [Na 2 O]: 19.9 wt%) in the form of SiO 2 The resulting cake was mechanically and chemically disintegrated by adding about 0.30% by weight of aluminum metal Al (about 0.03% by weight of Al is understood to come from the sodium silicate solution). The flow rate of the 7.7% by weight sulfuric acid solution was adjusted to maintain the pH of the reaction medium at a value of 6.3. The resulting slurry was dried by a nozzle spray dryer to obtain precipitated silica CS9.
[0260] The properties of the precipitated silica CS9 are reported in Table 1 below.
[0261] Comparative Example 10 (silica obtained according to the method described in WO 2018 / 202752 in the name of the Applicant) A 2500 L stainless steel reactor was charged with 1126 L of water and 29.7 kg of Na. 2 SO 4 (solid). The resulting solution was stirred and heated to reach 92°C. All reactions were carried out at this temperature. A 96% by weight sulfuric acid solution was introduced into the reactor until a pH value of 3.9 was reached. A sodium silicate solution (SiO ) with a flow rate of 420 L / h was added. 2 / Na 2 O ratio=3.45;SiO 2% sulfuric acid solution was introduced simultaneously over 14.9 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was at a value of 4.3. At the end of this step, a sodium silicate solution with a flow rate of 445 L / h and a 96% sulfuric acid solution with a flow rate of 9.45 L / h were introduced simultaneously. The flow rate of the 96% sulfuric acid solution was adjusted so that the pH of the reaction medium was at a value of 4.3.
[0262] The introduction of acid was then stopped while the addition of the sodium silicate solution was brought to a flow rate of 579 L / h until the reaction medium reached a pH value of 8.00.
[0263] Then, a sodium silicate solution with a flow rate of 708 L / h and a 96% by weight sulfuric acid solution were introduced simultaneously over a period of 3 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0264] At the same time, over a period of 14.8 minutes, (i) a sodium silicate solution at a flow rate of 706 l / h, (ii) a sodium aluminate solution ([Al]: 12.2 wt%, [Na 2 O]:19.4% by weight)(SiO 2 equivalent to about 1.40% by weight of aluminum metal relative to the weight of the reaction mixture), and (iii) a 96% sulfuric acid solution was introduced, the flow rate of the 96% sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.0.
[0265] At the end of this simultaneous addition, the pH of the reaction medium was brought to a value of 4.4 using 96% by weight sulfuric acid, then water was introduced, the temperature was reduced to 85° C. and the reaction mixture was aged for 5 minutes. A slurry was obtained.
[0266] The reaction slurry was filtered and washed with a filter press to give a precipitated silica cake of 23% solids by weight. The resulting silica cake then underwent a liquefaction step in a continuously vigorously stirred reactor. Then, 200 g of 7.7% aqueous sulfuric acid was added to the mixture to adjust the pH. The pH value of the liquefied cake was 6.0 and the solids content was 23 wt %.
[0267] The obtained slurry was dried by a nozzle type spray dryer to obtain precipitated silica Micropearl CS10.
[0268] The properties of the precipitated silica CS10 are reported in Table 1 below.
[0269] Comparative Example 11 (silica obtained according to the method described in WO 2009 / 112458 in the name of the Applicant) In a 25 L stainless steel reactor, 9.26 L of water, 136.6 g of Na 2 SO 4 (solid), and 4756 g of sodium silicate solution (SiO 2 / Na 2 O weight ratio=3.46, SiO 2 Concentration = 19.95% by weight. The same sodium silicate solution was used throughout the process. The reaction medium was stirred and heated to reach 92.5°C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium.
[0270] A 7.7% by weight solution of sulfuric acid was introduced at a flow rate of 110.7 g / min over a period of 17 minutes, after which the flow rate of the 7.7% by weight solution of sulfuric acid was adjusted to 321.0 g / min so as to bring the pH of the reaction medium to 8.0.
[0271] A sodium silicate solution at a flow rate of 95.3 g / min and a 7.7% by weight sulfuric acid solution were then simultaneously introduced over a period of 10 minutes, the flow rate of the 7.7% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0272] At the end of this step, the pH of the reaction medium was brought to a value of 4.05 using 7.7% by weight sulfuric acid over a period of 8 minutes.
[0273] A sodium silicate solution at a flow rate of 64.3 g / min and a 7.7% by weight sulfuric acid solution were then introduced simultaneously over a period of 28 minutes, the flow rate of the 7.7% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 4.05.
[0274] The introduction of acid was then stopped while the addition of the sodium silicate solution was maintained at a flow rate of 29 g / min over a period of 4.6 minutes until the reaction medium reached a pH value of 5.2. The reaction mixture was aged for 5 minutes. A slurry was obtained.
[0275] The slurry was filtered and washed with a filter press to obtain a precipitated silica cake with a solid content of 20 wt. %. The resulting silica cake was then added to a continuously vigorously stirred reactor with a sodium aluminate solution ([Al]: 11.6 wt. %, [Na 2 The liquefaction process was carried out while adding 7.7 wt% aqueous sulfuric acid solution to adjust the pH. 2 Weight ratio of aluminum metal to Al / SiO 2 (It is understood that about 0.03 wt% Al comes from the silicate solution.) The pH value of the liquefied cake was 6.4 and its solid content was 20%. The resulting slurry was dried by a nozzle type spray dryer to obtain precipitated silica powder.
[0276] Afterwards, the granulation step was performed. 150 g of silica powder was used per batch and introduced into the granulator (Alexanderwerk, granulator WP120Pharma). Silica granules were formed with an air gap of 3 mm, oil pressure of 20 bar and roller speed of 3-5 rpm. The granulator speed was fixed at 108 rpm to achieve a sieving of 1-2.5 mm. The duration of the granulation step was approximately 15 min per batch. As a result, precipitated silica granules CS11 were obtained.
[0277] The properties of the precipitated silica CS11 are reported in Table 1 below.
[0278] Comparative Example 12 (silica obtained according to the method described in WO 2011 / 026895 in the name of the Applicant) A 25 L stainless steel reactor was charged with 11.8 L of water. The reaction medium was stirred and heated until it reached 86° C. Then, sulfuric acid (concentration: 7.7% by weight) was introduced into the reactor with stirring, bringing the pH value to 4.0. The resulting solution was stirred and heated until it reached 92° C. The entire reaction was carried out at this temperature with stirring in order to maintain a homogeneous reaction medium.
[0279] Sodium silicate solution (SiO) at a flow rate of 57.5 g / min 2 / Na 2 O weight ratio=3.46;SiO 2 A 7.7 wt.% sulfuric acid solution with a concentration = 19.95 wt.% and a flow rate of 64.4 g / min was introduced simultaneously over 35 seconds. The same sodium silicate solution was used throughout the process. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was set to a value of 4.0. A gel point was observed during this step after 21 minutes. The silicate added after the gel point represented 40% of the total silicate added since the start of the reaction.
[0280] The introduction of acid was then stopped, while the addition of the sodium silicate solution was maintained at a flow rate of 38.3 g / min over 6 minutes, until the reaction medium reached a pH value of 8.00.
[0281] A sodium silicate solution at a flow rate of 57.6 g / min and a 7.7% by weight sulfuric acid solution were then simultaneously introduced over a period of 40 minutes, the flow rate of the 7.7% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0282] At the end of this step, the pH of the reaction medium was brought to a value of 4.00 using 7.7% by weight sulfuric acid over a period of 3.35 minutes.
[0283] A sodium silicate solution at a flow rate of 18.2 g / min and a 7.7% by weight sulfuric acid solution were then introduced simultaneously over a period of 81 minutes, the flow rate of the 7.7% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 4.00.
[0284] The introduction of acid was then stopped while the addition of the sodium silicate solution was maintained at a flow rate of 15 g / min over 6 minutes until the reaction medium reached a pH value of 5.2. The reaction mixture was aged for 5 minutes. A slurry was obtained.
[0285] The slurry is filtered and washed with a filter press to obtain a precipitated silica cake with a solid content of 20 wt. %. The resulting silica cake is then subjected to a liquefaction step in a continuously vigorously stirred reactor with the addition of a sodium aluminate solution ([Al]: 11.6 wt. %, [Na2O]: 19.9 wt. %) and a 7.7 wt. % aqueous sulfuric acid solution to adjust the pH. The silica cake contains about 0.33 wt. % SiO 2 Weight ratio of aluminum metal to Al / SiO 2 (It is understood that about 0.03 wt% Al comes from the silicate solution.) The pH value of the liquefied cake was 6.4 and its solid content was 20%. The resulting slurry was dried by a nozzle type spray dryer to obtain precipitated silica powder.
[0286] Afterwards, the granulation step was carried out. 150 g of silica powder was used per batch and introduced into the granulator (Alexanderwerk, granulator WP120Pharma). Silica granules were formed with an air gap of 3 mm, oil pressure of 20 bar and roller speed of 3-5 rpm. The granulator speed was fixed at 108 rpm to achieve a sieving of 1-2.5 mm. The duration of the granulation step was approximately 15 min per batch. As a result, precipitated silica granules CS12 were obtained.
[0287] The properties of the precipitated silica CS12 are reported in Table 1 below.
[0288] Example 13 (according to the invention) In a 2500 L stainless steel reactor, 1124 L of water and 29.9 kg of Na 2 SO 4(solid). The resulting solution was stirred and heated to reach 92°C. All reactions were carried out at this temperature. A 96% by weight sulfuric acid solution was introduced into the reactor until a pH value of 3.9 was reached. A sodium silicate solution (SiO ) with a flow rate of 408 L / h was added. 2 / Na 2 O ratio=3.44;SiO 2 Concentration=19.3% by weight was introduced into the reactor over a period of 54 seconds. The same sodium silicate solution was used throughout the process. Sodium silicate solution with a flow rate of 435 L / h, water with a flow rate of 581 L / h and a 96% by weight sulfuric acid solution were then introduced simultaneously over a period of 15 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was maintained at a value of 4.05. At the end of this step, sodium silicate solution with a flow rate of 435 L / h and a 96% by weight sulfuric acid solution were introduced simultaneously over a period of 4.1 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.05.
[0289] During this step of simultaneous addition of sodium silicate and acid, a gel point was observed after 9.3 minutes, and the amount of sodium silicate added after the gel point represented 53% of the total amount of sodium silicate added during the entire step.
[0290] The introduction of acid was then stopped while the addition of the sodium silicate solution was brought to a flow rate of 593 L / h until the reaction medium reached a pH value of 8.00.
[0291] Then, a sodium silicate solution with a flow rate of 706 L / h and a 96% by weight sulfuric acid solution were introduced simultaneously over a period of 22.5 minutes, the flow rate of the 96% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0292] At the end of this simultaneous addition, the pH of the reaction medium was brought to a value of 4.6 using 96% by weight sulfuric acid, then water was introduced, the temperature was reduced to 85° C. and the reaction mixture was aged for 5 minutes. A slurry was obtained.
[0293] The suspension was filtered and washed with a filter press to give a precipitated silica cake with a solids content of 22% by weight.
[0294] The silica cake thus obtained was treated with sodium aluminate solution ([Al]: 12.5 wt.%, [Na 2 The liquefaction step was carried out while adding 19.5% by weight of SiO and 7.7% by weight of sulfuric acid aqueous solution to adjust the pH. 2 Weight ratio of aluminum metal to Al / SiO 2 The amount of sodium aluminate solution was added to the target pH of the liquefied cake was 7.4 and the solids content was 22%. The obtained slurry was dried by a nozzle type spray dryer to obtain precipitated silica Micropearl S13.
[0295] The properties of the precipitated silica S13 are reported in Table 1 below.
[0296] Example 14 (according to the invention) A 2500 L stainless steel reactor was charged with 1123 L of water and 29.9 kg of Na. 2 SO 4 (solid) was introduced. The resulting solution was stirred and heated to reach 92°C. All reactions were carried out at this temperature. A 96% by weight sulfuric acid solution was introduced into the reactor until a pH value of 3.9 was reached. A sodium silicate solution (SiO ) with a flow rate of 408 L / h was added. 2 / Na 2 O ratio=3.44;SiO 2 % sulfuric acid solution was introduced simultaneously over 15 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was maintained at a value of 4.0. At the end of this step, a sodium silicate solution with a flow rate of 445 L / h and a 96% sulfuric acid solution with a flow rate of 4.0 L / h were introduced simultaneously over 4.0 minutes. The flow rate of the 96% sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.0.
[0297] During this step of simultaneous addition of sodium silicate and acid, a gel point was observed after 11.9 minutes, and the amount of sodium silicate added after the gel point represented 40% of the total amount of sodium silicate added during the entire step.
[0298] The introduction of acid was then stopped while the addition of the sodium silicate solution was brought to a flow rate of 608 L / h until the reaction medium reached a pH value of 8.00.
[0299] Then, a sodium silicate solution with a flow rate of 707 L / h and a 96% by weight sulfuric acid solution were introduced simultaneously over a period of 22.5 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0300] At the end of this simultaneous addition, the pH of the reaction medium was brought to a value of 4.70 using 96% by weight sulfuric acid, then water was introduced, the temperature was reduced to 85° C. and the reaction mixture was aged for 5 minutes. A slurry was obtained.
[0301] The reaction slurry was filtered and washed with a filter press to give a precipitated silica cake of 23% solids by weight.
[0302] The silica cake thus obtained was then subjected to a liquefaction step in a reactor under continuous and vigorous stirring, with the addition of a sodium aluminate solution ([Al]: 12.5 wt%, [Na2O]: 19.5 wt%) and a 7.7 wt% sulfuric acid solution to adjust the pH. 2 Weight ratio of aluminum metal to Al / SiO 2 The amount of sodium aluminate solution was added to the target pH of the liquefied cake was 6.1 and the solids content was 23%.
[0303] The obtained slurry was dried by a nozzle type spray dryer to obtain precipitated silica Micropearl S14.
[0304] The properties of the precipitated silica S14 are reported in Table 1 below.
[0305] Example 15 (according to the invention) In a 25 L stainless steel reactor, 15.3 L of water and 359 g of Na 2 SO 4 (solid) was introduced. The resulting solution was stirred and heated to reach 92° C. The entire reaction was carried out at this temperature with stirring to maintain a homogeneous reaction medium. Sulfuric acid (concentration: 7.7% by weight) was introduced into the reactor until a pH value of 3.8 was reached.
[0306] Sodium silicate solution (SiO 2 / Na 2 O weight ratio=3.46;SiO 2 A solution of sodium silicate with a flow rate of 109.6 g / min and a 7.7% by weight sulfuric acid solution with a flow rate of 153.3 g / min were then simultaneously introduced over a period of 12.75 minutes. The flow rate of the sulfuric acid was adjusted so that the pH of the reaction medium was set to a value of 4.1. During this step, a gel point was observed after 11.7 minutes. At the end of this step, a solution of sodium silicate with a flow rate of 105.9 g / min and a 96% by weight sulfuric acid solution were simultaneously introduced over a period of 4.07 minutes. The flow rate of the 96% by weight sulfuric acid solution was adjusted so that the pH of the reaction medium was maintained at a value of 4.1. The silicate added after the gel point represented 30% of the total silicate added since the start of the reaction.
[0307] The introduction of acid was then stopped while the addition of the sodium silicate solution was maintained at a flow rate of 169.6 g / min over 1.35 minutes until the reaction medium reached a pH value of 8.00.
[0308] Then, a sodium silicate solution with a flow rate of 173.6 g / min and a 96% by weight sulfuric acid solution were introduced simultaneously over a period of 22.60 minutes, the flow rate of the 96% by weight sulfuric acid solution being adjusted so as to maintain the pH of the reaction medium at a value of 8.00.
[0309] At the end of this step, the pH of the reaction medium was brought to a value of 4.64 using 96% by weight sulfuric acid. The reaction mixture was aged for 5 minutes. A slurry was obtained.
[0310] The slurry was filtered and washed with a filter press to obtain a precipitated silica cake with a solid content of 20 wt. %. The silica cake thus obtained was then treated with a sodium aluminate solution ([Al]: 11.6 wt. %, [Na 2 The liquefaction process was carried out with the addition of 19.9 wt% SiO and 7.7 wt% sulfuric acid solution to adjust the pH. 2 Weight ratio of aluminum metal to Al / SiO 2 (It is understood that about 0.03 wt% Al comes from the silicate solution.) The pH value of the liquefied cake was 6.4 and its solid content was 20%. The resulting slurry was dried by a nozzle type spray dryer to obtain precipitated silica powder.
[0311] Afterwards, the granulation step was carried out. 150 g of silica powder was used per batch and introduced into the granulator (Alexanderwerk, granulator WP120Pharma). Silica granules were formed with an air gap of 3 mm, oil pressure of 20 bar and roller speed of 3-5 rpm. The granulator speed was fixed at 108 rpm to achieve a sieving of 1-2.5 mm. The duration of the granulation step was approximately 15 min per batch. As a result, precipitated silica granules S15 were obtained.
[0312] The properties of the precipitated silica S15 are reported in Table 1 below.
[0313] [Table 3]
[0314] Example 16: Use of Silica in Elastomer Compositions material Two silicas according to the invention (namely silicas S2 and S8 from Examples 2 and 8 above) were evaluated in an SBR / BR model tire tread compound in comparison with a prior art silica grade, namely ULTRASIL® 9100GR and two silicas obtained according to WO 03 / 016215 in the name of the Applicant (namely silicas CS1 and CS9 as described in Comparative Examples 1 and 9 above). The compositions, expressed in parts by weight per 100 parts of elastomer (phr), are given in Tables II and III below.
[0315] [Table 4]
[0316] [Table 5]
[0317] Process for preparing rubber composition The preparation of the rubber composition was carried out in two successive preparation stages: a first stage of high temperature thermomechanical processing, followed by a second stage of mechanical processing at a temperature below 110° C. to introduce the vulcanization system. The first stage was carried out using a mixing device of the Brabender brand internal mixer type (volume of 380 mL).
[0318] In the first pass of the first stage, the elastomer and reinforcing filler (introduced in portions) were mixed with the coupling agent, plasticizer, stearic acid, 6-PPD, DPG, and ZnO for a time of 4 minutes 30 seconds for the compounds in Table II and 4 minutes 45 seconds for the compounds in Table III, with a drop temperature of about 160°C.
[0319] After cooling the mixture (to a temperature below 100°C), the vulcanization system was added during a second stage. This was done in an open mill preheated to 50°C. 20 cuts were made to ensure good homogeneity of the vulcanization system in the compound. The duration of this stage was 2-6 minutes. Each final mixture was then calendered into plaques of 2-3 mm thickness.
[0320] Properties of the vulcanizate Measurements were taken after vulcanization at 150°C for 50 minutes for the compounds in Table II and for 1 hour for the compounds in Table III.
[0321] Uniaxial tensile tests were carried out on H2 type specimens in an Instron 5564 machine at a speed of 500 mm / min according to the instructions of standard NF ISO 37. The x% modulus, which corresponds to the stress measured at x% tensile strain, is expressed in MPa. The tensile strength is expressed in MPa and the elongation at break is expressed in MPa.
[0322] The reinforcement index (RI), equal to the ratio of the modulus at 300% strain to the modulus at 100% strain, was determined.
[0323] The loss factor (tan δ) and the amplitude of the elastic modulus in dynamic shear (ΔG') were measured for vulcanized samples (parallel hexahedral specimens: cross-sectional area 8 mm 2 The measurements were recorded at different strain amplitudes (length, width, and height 7 mm). The samples were subjected to a double alternating sinusoidal shear strain at a temperature of 40° C. and a frequency of 10 Hz. The strain amplitude sweep process was performed according to a forward-return cycle going outwards from 0.1% to 50% and then back from 50% to 0.1%. The values reported in Tables IV and V are obtained from the return strain amplitude scan and relate to the maximum value of the loss factor (tan δmax) and the amplitude of the elastic modulus (ΔG') between values of 0.1% and 50% of the strain (Payne effect). The measurements were performed on a Metravib DMA+1000 according to standard ASTM D5992.
[0324] The results are summarized in Tables IV and V below.
[0325] [Table 6]
[0326] [Table 7]
[0327] The silica according to the invention allows for a more balanced wear performance (reinforcement index, tensile strength, elongation at break) / rolling resistance (Payne effect, Tan δmax) trade-off.
[0328] Example 17: Use of Silica in Elastomer Compositions material The silicas according to the invention (i.e. silicas S13, S14 and S15 of Examples 13, 14 and 15 above) were evaluated in SBR / BR model compounds in comparison with prior art silica grades, namely (i) ZEOSIL® 1165MP (abbreviated "Z1165MP"), (ii) a silica obtained according to WO 18202752 in the name of the Applicant (i.e. silica CS10 as described in Comparative Example 10), (iii) a silica according to WO 09112458 in the name of the Applicant (i.e. silica CS11 as described in Comparative Example 11) and (iv) a silica according to WO 11026895 in the name of the Applicant (i.e. silica CS12 as described in Comparative Example 12). The compositions, expressed in parts by weight per 100 parts of elastomer (phr), are given in Tables VI and VII below.
[0329] [Table 8]
[0330] [Table 9]
[0331] Process for preparing rubber composition The preparation of the rubber composition was carried out in two successive preparation stages: a first stage of high temperature thermomechanical processing, followed by a second stage of mechanical processing at a temperature below 110° C. to introduce the vulcanization system. The first stage was carried out using a mixing device of the Brabender brand internal mixer type (volume of 380 mL).
[0332] In the first pass of the first stage, the elastomer and reinforcing filler (introduced in portions) were mixed with the coupling agent, plasticizer, stearic acid, 6-PPD, DPG, and ZnO. The mixing time was 4 minutes 30 seconds for the compounds in Table VI and 5 minutes for the compounds in Table VII, and the drop temperature was about 160° C. for all compounds.
[0333] After the mixture had cooled (to a temperature below 100° C.), the vulcanization system was added during a second stage, which was carried out on an open mill preheated to 50° C. The duration of this stage was 2 to 6 minutes. Each final mixture was then calendered into plaques of thickness 2 to 3 mm.
[0334] Properties of the vulcanizate Measurements were made after a 40 minute cure at 160°C for the compounds in Table VI and after a 50 minute cure at 150°C for the compounds in Table VII.
[0335] The tensile strength, elongation at break, and tan δmax were measured in the same manner as described above in Example 16.
[0336] After crosslinking, the Z value was measured according to the method described by S. Otto et al. in Kautschuk Gummi Kunststoffe, 58 Jahrgang, NR 7-8 / 2005, in accordance with ISO 11345. The percentage of "undispersed area" was calculated using a camera observing the surface of the sample with light incidence at 30°. The bright spots are associated with charges and aggregates, while the dark spots are associated with the rubber matrix. By digital processing, the image is converted into a black and white image, and the percentage of "undispersed area" can be determined, as described by S. Otto in the above cited reference. The higher the Z value, the better the distribution of the charges in the elastomer matrix (Z value 100 corresponds to perfect distribution, Z value 0 corresponds to very poor distribution). The calculation of the Z value was based on the percentage of the area where the charges were not distributed, measured by an apparatus DisperGrader® 1000 with operating mode and operating software DisperData from Dynisco, according to the formula: Z=100-(percentage of undispersed area) / 0.35.
[0337] The results are summarized below in Tables VIII and IX.
[0338] [Table 10]
[0339] [Table 11]
[0340] Compared to the commercial silica grade Zeosil® 1165MP, the silicas S13, S14 and S15 according to the invention were able to significantly reduce the energy dissipation (tan δmax) while retaining a high level of reinforcement, including high dispersibility (Z index), high tensile strength and high elongation at break.
[0341] Compared to the prior art silicas CS10, CS11 and CS12, the silicas S13, S14 and S15 according to the invention showed much improved dispersibility, higher tensile strength and higher elongation at break, while retaining a low level of energy dissipation.
[0342] Overall, the silica according to the invention exhibited a much better balance of properties (a compromise between wear resistance and energy dissipation capacity) than the silicas of the prior art.
Claims
1. Features: ・40 to 300 m 2 / g range of CTAB surface area; Average size d of less than 11 nm as measured by SAXS ZS Primary particles having the formula: -Measured by centrifugal sedimentation |d 50 |<-0.782×|CTAB|+255(I) The median particle size d 50 ; Precipitated silica having
2. 50 to 300 m 2 / g, preferably 70 to 300 m 2 / g, more preferably 80 to 270 m 2 / g, or 120 to 275 m 2 2. The precipitated silica of claim 1, having a CTAB surface area of 1.0 to 1.0 g / g.
3. 150m 2 / g or greater than 210m 2 3. The precipitated silica of claim 2 having a CTAB surface area of less than 1 / g.
4. d of 50 to 200 nm, preferably 75 to 150 nm 50 4. The precipitated silica of claim 1, 2 or 3, having the formula:
5. d from 85 to 130 nm 50 5. The precipitated silica of claim 4, having
6. The formula: 84 |d 84 |<-2.08×|CTAB|+659(II) Characterized by d 84 6. Precipitated silica according to claim 1, having the formula:
7. d between 120 and 430 nm, preferably between 150 and 400 nm 84 7. The precipitated silica of claim 6, having
8. 8. Precipitated silica according to any one of claims 1 to 7, comprising at least one element selected from Al, Ga, B, Sc, Y, Ti, Zr, Hf, V, Nb, Ta, Fe, Co, Mg, Ca or Zn.
9. 9. Precipitated silica according to claim 1, having an FWHM such that |FWHM|<250-0.815*|CTAB|(III).
10. 10. Precipitated silica according to claim 1, having a fine particle fraction τf such that |τf|>=0.045×|CTAB|+84(IV).
11. A precipitated silica according to any one of claims 1 to 10, in powder form.
12. 11. Precipitated silica according to claim 1, in the form of micropearls.
13. 11. Precipitated silica according to claim 1, in granular form.
14. 1. A process for the preparation of precipitated silica, comprising the steps of: (i) providing a starting solution having a pH between 2.00 and 5.50; (ii) adding silicate and acid simultaneously to said starting solution to obtain a reaction medium whose pH is maintained in the range of 2.00 to 5.50; (iii) stopping the addition of the acid and the silicate and adding a base to the reaction medium to increase the pH of the reaction medium to a value between 7.00 and 10.00; (iv) simultaneously adding a silicate and an acid to the reaction medium such that the pH of the reaction medium is maintained in the range of 7.00 to 10.00; (v) continuing said addition of said acid to said reaction medium while stopping the addition of said silicate to allow the pH of said reaction medium to reach less than 6.00 to obtain a suspension of precipitated silica; Including, A process wherein a gel point is reached during step (ii) and the amount of said silicate added during step (ii) after reaching said gel point is between 5% and 55% of the total amount of said silicate added at the end of step (ii).
15. 15. The method of claim 14, wherein a dilute acid is used until the gel point is reached and a concentrated acid is used after the gel point is reached.
16. 16. The process according to claim 14 or 15, wherein the amount of silicate added to the reaction medium during step (iv) is at least 55% of the total amount of silicate required for the reaction.
17. A method according to any one of claims 14 to 16, wherein an intermediate step (ii') is carried out between steps (i) and (ii), in which a silicate is added to the starting solution.
18. 18. The method according to any one of claims 14 to 17, wherein the precipitated silica is a precipitated silica according to any one of claims 1 to 13.
19. 14. Use of the precipitated silica according to any one of claims 1 to 13 as a catalyst, catalyst support, absorbent for active substances, in particular carriers for liquids used in foods, in particular vitamins (vitamin E or choline chloride), or as a viscosity modifier, anti-blocking agent or anti-caking agent, or as an additive for toothpaste, concrete or paper, or in the manufacture of thermal insulation materials or in the preparation of resorcinol-formaldehyde / silica composite materials.
20. Use of the precipitated silica according to any one of claims 1 to 13 for the preparation of a filled polymer composition.
21. A composition comprising a precipitated silica according to any one of claims 1 to 13 and at least one polymer.
22. The precipitated silica is present in an amount W of less than 0.50 wt.%, typically less than 0.45 wt.%, typically at least 0.01 wt.% and less than 0.50 wt.%. Al 22. The composition of claim 21, which contains aluminum.
23. 23. The composition of claim 22, wherein the at least one polymer is one or more elastomers.
24. 24. Use of a composition according to claim 22 or 23 for the manufacture of a part of a tyre.
25. 25. The use according to claim 24, wherein said portion of a tire is a tire tread.
26. A portion of a tire comprising the composition of claim 22 or 23.
27. 27. The part of claim 26 which is a tire tread.
28. 28. A tire comprising a portion according to claim 26 or 27.
29. 29. An article, generally a vehicle, comprising a tire according to claim 28.
30. 22. Use of the composition of claim 21 for the manufacture of a finished product other than any part of a tire, any finished product other than a tire, and any finished product other than any article comprising a tire.
31. 31. The use according to claim 30, wherein the finished product is selected from the group consisting of footwear soles, flooring, engineering parts, seals, pipes, sheaths, cables, supports, separators, and belts.
32. 22. A finished article other than any portion of a tire, any finished article other than a tire, and any finished article other than an article including a tire, comprising or consisting of at least one portion of the composition of claim 21.
33. 33. The finished product of claim 32, selected from the group consisting of footwear soles, flooring, engineering parts, seals, pipes, sheathing, cables, supports, separators, and belts.
34. 22. Use according to claim 21 in shoe soles, floor coverings, gas barriers, flame retardant materials, engineering parts, e.g. rollers for aerial cables, seals for household appliances, seals for piping of liquids or gases, brake system seals, pipes (flexible), sheaths (especially cable sheaths), cables, engine supports, battery separators, conveyor belts or transmission belts.